toner
By adjusting the viscoelasticity of the toner and controlling its glass transition temperature and tan δ curve slope range, the problem of the toner's difficulty in achieving low-temperature fixation and storage performance balance in high-quality and high-speed printing is solved, and the toner's low-temperature fixation and storage performance is improved.
Patent Information
- Application Number
- JP2021574134
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-01-29
AI Technical Summary
The prior art is difficult to achieve a good balance between low-temperature fixation and storage performance of toner while printing at high quality and high speed.
By adjusting the viscoelasticity of the toner, the specific method is to control its glass transition temperature (Tg) between 45°C and 100°C and meet a specific slope range through the tanδ curve measured by dynamic viscosity to improve the low-temperature fixation and storage performance of the toner.
The toner is well fixed performance under low temperature conditions and blocking performance in long-term storage, avoiding the problem of blocking and excessive fixed temperature in the storage process.
Smart Images

Figure 0007647587000005 
Figure 0007647587000006 
Figure 0007647587000007
Abstract
Description
[Technical field]
[0001] This disclosure relates to toners used to develop electrostatic latent images in processes such as electrophotography, electrostatography, and electrostatic printing. [Background technology]
[0002] In image forming devices such as electrophotographic devices, electrostatic recording devices, and electrostatic printing devices, an electrostatic latent image formed on a photoconductor is developed with toner, the toner image is transferred onto a transfer material such as paper, and then fixed by heating or the like to form a fixed image. In such image forming apparatuses, there is a demand for toners capable of forming high-quality images, which can meet the demands of higher image quality and higher printing speed. In recent years, attempts have been made to develop toners that focus on the viscoelasticity of binder resins or toners.
[0003] For example, in Patent Document 1, the binder resin contained in the toner has a loss modulus (G") of 1×10 4 Between the temperatures at which the tan δ of the binder resin becomes 1.2 Pa, there is a minimum of tan δ of the binder resin, the minimum value of tan δ is less than 1.2, and the storage modulus (G') at the temperature at which the tan δ is minimum is G'=5×10 5 Pa or more, and G”=1×10 4 It is disclosed to use a polyester resin having a tan δ value of 3.0 or more at a temperature where the viscosity becomes 1 Pa.
[0004] Patent Document 2 discloses an image forming method using a fixing member having a surface layer in which an anti-wear additive with a volume average particle size of 1 μm or less is dispersed, in combination with a toner having a tan δ peak in a range of 40° C. to 70° C. and having a peak value of less than 2.0 in a dynamic viscoelastic temperature dependency measurement. Patent Document 2 discloses, as a method for controlling the peak value to less than 2.0, a method of using an amorphous polyester resin as a binder resin for the toner and further dispersing fine particles with a particle size of 0.1 μm or less in the toner, and a method of using a combination of a crystalline polyester resin and an amorphous polyester resin as a binder resin for the toner.
[0005] Patent Document 3 discloses a toner for developing electrostatic images, which contains a binder resin, a colorant, a release agent, and a charge control agent, the release agent containing a wax having a polar group, and which has a tan δ value of 1 to 2 at 80 to 145° C., measured by a viscoelasticity measuring device at a frequency of 10 kHz and a shear stress of 500 Pa, and a breaking point is observed at 180° C. or less on a temperature-tan δ curve. Patent Document 3 also describes that it is preferable to use a polyester resin as the binder resin. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-194542 [Patent Document 2] JP 2009-151005 A [Patent Document 3] JP 2013-88503 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the case of toners capable of forming high-quality images, although both low-temperature fixability and storability are required to be excellently balanced, it has been difficult to improve both the low-temperature fixability and storability of toners well-balancedly by the conventional methods for adjusting the viscoelasticity of binder resins or toners. An object of the present disclosure is to provide a toner excellent in low-temperature fixability and storability.
Means for Solving the Problems
[0008] As a result of intensive studies to achieve the above object, the present inventor has found that there are viscoelastic properties of a toner that can efficiently improve the low-temperature fixability of the toner and suppress blocking during storage, leading to the present disclosure.
[0009] That is, the toner of the first present disclosure is a toner containing colored resin particles including a binder resin, a colorant, a softening agent, and a charge control agent, and an external additive, The glass transition temperature (Tg) specified from the temperature dependence curve of the loss tangent (tanδ) of the toner obtained by dynamic viscoelastic measurement at a measurement frequency of 24 Hz satisfies 45°C < Tg (°C) < 100°C, In the temperature dependence curve of the loss tangent (tanδ), when the loss tangent (tanδ) at 45°C is tanδ(45°C), the loss tangent (tanδ) at the glass transition temperature (Tg) is tanδ(Tg), the loss tangent (tanδ) at 100°C is tanδ(100°C), and the loss tangent (tanδ) at 130°C is tanδ(130°C), Equation (I-1): 5.00×10 -2 <(tanδ(Tg) - tanδ(45°C)) / (Tg - 45) < 7.60×10 -2 And Equation (I-2): -3.0×10 -3 <(tanδ(130°C) - tanδ(100°C)) / 30 < 9.8×10 -1 It is characterized by satisfying.
[0010] In the toner of the first disclosure, the softening temperature (T 2 ) in the 1 / 2 method measured by a flow tester under the condition of a pressure of 10.0 kgf / cm 1 / 2 may exceed 154°C and be less than 220°C.
[0011] In the toner of the first disclosure, the loss tangent (tanδ) at the glass transition temperature (Tg) may be less than 1.870.
[0012] In the toner of the first disclosure, in the temperature dependence curve of the loss tangent (tanδ), the loss tangent (tanδ) at 100°C may be 0.800 or more and 1.100 or less, and the loss tangent (tanδ) at 130°C may be 0.800 or more and 1.280 or less.
[0013] In the toner of the first disclosure, the binder resin may contain a polymer of one or more polymerizable monomers including at least one monovinyl monomer selected from the group consisting of styrene, acrylic ester, and methacrylic ester.
[0014] In the toner of the first disclosure, the weight average molecular weight of the polymer contained in the binder resin may be 3.00×10 5 or more and 7.00×10 5 or less.
[0015] Also, the toner of the second disclosure is a toner containing colored resin particles including a binder resin, a colorant, a softening agent, and a charge control agent, and an external additive, wherein the glass transition temperature (Tg) specified from the temperature dependence curve of the loss tangent (tanδ) of the toner obtained by dynamic viscoelastic measurement at a measurement frequency of 24 Hz satisfies 45°C < Tg (°C) < 100°C, In the temperature dependency curve of the loss tangent (tanδ), when the loss tangent (tanδ) at 45°C is tanδ(45°C), the loss tangent (tanδ) at the glass transition temperature (Tg) is tanδ(Tg), the loss tangent (tanδ) at 100°C is tanδ(100°C), and the loss tangent (tanδ) at 130°C is tanδ(130°C), Formula (II-1): 5.00×10 -2 <(tanδ(Tg)-tanδ(45℃)) / (Tg-45)<7.60×10 -2 and Formula (II-2): 2.1×10 -3 <(tanδ(130℃)-tanδ(100℃)) / 30<4.4×10 -2 The present invention is characterized in that:
[0016] In the second toner of the present disclosure, the toner may have an apparent glass transition temperature (Tg2) of 68°C to 74°C when heated at a heating rate of 1000 K / sec, and a heat generation initiation temperature of 50°C to 62°C when cooled at a cooling rate of 1000 K / sec, as measured by differential scanning calorimetry using a high-speed differential scanning calorimeter.
[0017] In the second toner of the present disclosure, the toner was subjected to a flow test at a pressure of 5.0 kgf / cm 2 The softening temperature (T 1 / 2 ) may be more than 124°C and less than 159°C.
[0018] In the second toner of the present disclosure, the loss tangent (tan δ) at the glass transition temperature (Tg) may be less than 2.410.
[0019] In the second toner of the present disclosure, in the temperature dependency curve of the loss tangent (tan δ), the loss tangent (tan δ) at 100° C. may be 0.900 or more and 1.400 or less, and the loss tangent (tan δ) at 130° C. may be 1.000 or more and 2.500 or less.
[0020] In the toner of the second present disclosure, the binder resin may contain a polymer of one or more polymerizable monomers including at least one monovinyl monomer selected from the group consisting of styrene, acrylic acid ester, and methacrylic acid ester.
[0021] In the toner of the second present disclosure, the weight average molecular weight of the polymer contained in the binder resin is 2.00×10 4 or more and 1.00×10 5 or less.
Advantages of the Invention
[0022] According to the present disclosure, a toner excellent in low-temperature fixability and storage stability can be provided.
Brief Description of the Drawings
[0023] [Figure 1] FIG. 1 is a diagram showing the temperature dependence curve of the loss tangent (tanδ) of the toner of Example I-1. [Diagram 2] FIG. 2 is a diagram showing the temperature dependence curve of the loss tangent (tanδ) of the toner of Example II-1. [Diagram 3] FIG. 3 is a diagram showing the method for obtaining the apparent glass transition temperature (Tg2) of the toner during heating and the heat generation start temperature of the toner during cooling in high-speed differential scanning calorimetry.
Modes for Carrying Out the Invention
[0024] I. Toner of the First Present Disclosure The toner of the first present disclosure is a toner containing colored resin particles including a binder resin, a colorant, a softening agent, and a charge control agent, and an external additive, and the glass transition temperature (Tg) specified from the temperature dependence curve of the loss tangent (tanδ) of the toner obtained by dynamic viscoelastic measurement at a measurement frequency of 24 Hz satisfies 45°C < Tg (°C) < 100°C, In the temperature dependency curve of the loss tangent (tanδ), when the loss tangent (tanδ) at 45°C is tanδ(45°C), the loss tangent (tanδ) at the glass transition temperature (Tg) is tanδ(Tg), the loss tangent (tanδ) at 100°C is tanδ(100°C), and the loss tangent (tanδ) at 130°C is tanδ(130°C), Formula (I-1): 5.00 x 10 -2 <(tanδ(Tg)-tanδ(45℃)) / (Tg-45)<7.60×10 -2 and Formula (I-2): -3.0 x 10 -3 <(tanδ(130℃)-tanδ(100℃)) / 30<9.8×10 -1 The present invention is characterized in that:
[0025] Below, the viscoelastic properties of the toner of the first disclosure, the manufacturing method of the colored resin particles used in the toner of the first disclosure and the colored resin particles, the external additives used in the toner of the first disclosure, and the performance of the toner of the first disclosure will be described in order. In this disclosure, the use of "to" in a numerical range means that the numerical values before and after it are included as the lower limit and upper limit.
[0026] I-1. Viscoelastic properties of the toner of the first disclosure The toner of the first disclosure has the following characteristic in the line shape of the temperature dependency curve of the loss tangent (tan δ) in the range of 45° C. to 145° C. obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. That is, it has at least one peak in the range of more than 45° C. and less than 100° C., and when the temperature at which tan δ of the peak is maximum is exceeded, tan δ decreases with increasing temperature, and then tan δ decreases or continues to decrease while increasing or decreasing, until tan δ reaches a minimum value, or tan δ becomes a constant value at a certain temperature, or tan δ continues to decrease. When tan δ reaches a minimum value, tan δ increases slowly with further temperature increase from the temperature at which the minimum value is reached, and continues to increase or becomes an almost constant value at a certain temperature or above. Furthermore, in the toner of the first disclosure, the glass transition temperature (Tg) specified from the temperature dependency curve of the loss tangent (tan δ) is more than 45° C. and less than 100° C., and in the temperature dependency curve of the loss tangent (tan δ), when the loss tangent (tan δ) at 45° C. is tan δ(45° C.), the loss tangent (tan δ) at the glass transition temperature (Tg) is tan δ(Tg), the loss tangent (tan δ) at 100° C. is tan δ(100° C.), and the loss tangent (tan δ) at 130° C. is tan δ(130° C.), Formula (I-1): 5.00 x 10 -2 <(tanδ(Tg)-tanδ(45℃)) / (Tg-45)<7.60×10 -2 and Formula (I-2): -3.0 x 10 -3 <(tanδ(130℃)-tanδ(100℃)) / 30<9.8×10 -1 Meet the following. In the present disclosure, the loss tangent (tan δ) is defined as the ratio (G″ / G′) of the storage modulus (G′) to the loss modulus (G″) measured by dynamic viscoelasticity measurement. In this disclosure, in accordance with Rule B of JIS Z8401:1999, the value of tan δ is rounded to three decimal places, and in the formulas (I-1) and (I-2), the values of tan δ are rounded to three decimal places. The value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) shown in the formula (I-1) is rounded to three significant digits, and the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (I-2) is rounded to two significant digits. In the present disclosure, the glass transition temperature (Tg) of the toner is specified as the lowest temperature at which tan δ becomes a maximum value in the lowest-temperature peak among one or more peaks in the temperature range of more than 45°C and less than 100°C in the temperature dependency curve of the loss tangent (tan δ) of the toner obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. Small fluctuations up and down due to measurement noise, etc. are not interpreted as the peak. In the present disclosure, the temperature dependency curve of the loss tangent (tan δ) obtained by dynamic viscoelasticity measurement may be referred to as a temperature-tan δ curve.
[0027] In the first toner of the present disclosure, the dynamic viscoelasticity measurement is performed using a rotating plate type rheometer (ARES-G2, manufactured by TA Instruments) using a parallel plate or a crosshatch plate under the following conditions. Frequency: 24Hz Sample set: The test piece (diameter 8 mm, thickness 2 to 4 mm) is clamped between 8 mmφ plates with a load of 20 g. The temperature is raised to 80°C to fuse the test piece to the jig, then the temperature is returned to 45°C and heating begins. Heating rate: 5℃ / min Temperature range: 45℃ to 150℃ The test piece can be prepared, for example, by pouring 0.2 g of the toner of the first disclosure into a cylindrical molding machine with a diameter of 8 mm, and applying pressure at 1.0 MPa for 30 seconds to form a cylindrical molding with a thickness of 2 to 4 mm and a diameter of 8 mm.
[0028] The toner of the first disclosure has a specific viscoelasticity that satisfies the formula (I-1) and the formula (I-2) in the temperature-tan δ curve, and thus has both low-temperature fixability and storage stability in a well-balanced manner, and is a toner with excellent performance that has been difficult to achieve in the past. The formula (I-1) indicates the range of the slope of the line passing through tan δ (45°C) and tan δ (Tg) in the temperature-tan δ curve, and the formula (I-2) indicates the range of the slope of the line passing through tan δ (100°C) and tan δ (130°C). The toner does not suddenly deform when it reaches a certain temperature during fixing and storage, but gradually deforms with the increase in temperature or with the passage of time when it is held at a certain temperature. Based on such properties of the toner, the present inventors have found that the property of a toner that provides a good balance between low-temperature fixability and storage stability is expressed in the slope of the line passing through tan δ(45° C.) and tan δ(Tg) and the slope of the line passing through tan δ(100° C.) and tan δ(130° C.). As a result of further intensive research, the present inventors have found that by adjusting the slope of the line passing through tan δ(45° C.) and tan δ(Tg), the blocking properties when the toner is stored for a long period of time can be easily controlled, and by adjusting the slope of the line passing through tan δ(100° C.) and tan δ(130° C.), the fixability of the toner can be easily controlled. The smaller the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) shown in the formula (I-1) is within the above-mentioned range, the easier it is to suppress blocking during toner storage, and the storage stability is improved. The smaller the difference between tan δ(Tg) and tan δ(45°C) and the higher the Tg, the smaller the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) is. It is presumed that the viscosity of the toner is not too strong, that is, the movement of polymer chains between toner particles is suppressed, and thus blocking is suppressed. In addition, it is presumed that the decrease in elasticity at low temperatures is suppressed, and thus blocking is suppressed. Furthermore, the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) is less than the above-mentioned upper limit in the formula (I-1), and thus deterioration of the storage stability of the toner is suppressed. When the value in formula (I-1) is greater than the lower limit, an increase in the fixing temperature is easily suppressed, and therefore deterioration of low-temperature fixing ability is suppressed. On the other hand, the larger the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (I-2) is within the above numerical range, the lower the fixing temperature tends to be, and the lower temperature fixing property is improved. When fixing the toner, the toner gradually deforms with the rise in temperature. When actually fixing the toner, there is a temperature gradient from at least 100°C to 130°C from when the paper to which the toner has been transferred enters the roll until it is discharged. It is presumed that the larger the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (I-2) is, the faster the rise in tan δ after the toner is heated, that is, the faster the increase in the viscosity of the toner, and thus fixing at a relatively low temperature becomes possible. Furthermore, by exceeding the lower limit in the formula (I-2), the glossiness of the formed image becomes good. On the other hand, by being less than the upper limit in the formula (I-2), blocking during toner storage is suppressed, and deterioration of storage stability is suppressed. The present inventors have also found that the toner having viscoelasticity that satisfies the above formula (I-1) and the above formula (I-2) in the temperature-tan δ curve exhibits the above-mentioned effects, particularly when the toner is subjected to a pressure of 10.0 kgf / cm using a flow tester. 2The toner softening temperature (T 1 / 2 ) is found to be greater than 154°C and less than 220°C.
[0029] In order to obtain a toner having a viscoelasticity that satisfies the above formula (I-1) and formula (I-2) in the temperature-tan δ curve, for example, the composition, molecular weight, and content of the binder resin contained in the toner, the type and content of the colorant, the viscosity of the colorant raw material, the glass transition temperature (Tg) and content of the charge control agent, the type and molecular weight of the softener, and the type and content of the external additive, etc., can be appropriately changed to control the viscoelasticity of the toner. Among them, it is effective to adjust the molecular weight and composition of the binder resin, the type and content of the colorant, and the viscosity of the colorant raw material. The molecular weight and composition, etc. of the binder resin contained in the toner have a large effect on the viscoelasticity of the toner in a low temperature range below the glass transition temperature. Therefore, in order to obtain a viscoelasticity that satisfies the above formula (I-1), it is effective to adjust the molecular weight and composition, etc. of the binder resin contained in the toner. On the other hand, the type and content of the colorant contained in the toner, and the viscosity, etc. of the colorant raw material have a large effect on the viscoelasticity of the toner in a temperature range of 100°C to 130°C. Therefore, in order to obtain a viscoelasticity that satisfies the formula (I-2), it is effective to adjust the type and content of the colorant contained in the toner, and the viscosity of the colorant raw material, etc. More specifically, by adopting a preferred form of each component described later, the temperature-tan δ curve of the toner can be made to satisfy the formulas (I-1) and (I-2).
[0030] The toner of the first disclosure satisfies the following formula (I-1) in a temperature-tan δ curve obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. Formula (I-1): 5.00 x 10 -2 <(tanδ(Tg)-tanδ(45℃)) / (Tg-45)<7.60×10 -2 In particular, the upper limit in the formula (I-1) is preferably 7.40×10 because blocking during storage of the toner is easily suppressed and storage stability is easily improved. -2is preferably less than 7.20×10 -2 and more preferably less than. On the other hand, from the viewpoint that the increase in the fixing temperature is easily suppressed, the lower limit in the formula (I-1) is 5.60×10 -2 is preferably at least, and 6.00×10 -2 is more preferably at least.
[0031] The toner of the first disclosure satisfies the following formula (I-2) in the temperature-tanδ curve obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. Formula (I-2): -3.0×10 -3 <(tanδ(130°C) - tanδ(100°C)) / 30 < 9.8×10 -1 Among them, from the viewpoints of improving the low-temperature fixability of the toner and the glossiness of the formed image being likely to be good, the lower limit in the formula (I-2) is preferably more than -1.5×10 -3 and more preferably more than 0.1×10 -3 On the other hand, from the viewpoint that the deterioration of the storage stability is easily suppressed, the upper limit in the formula (I-2) is preferably less than 5.0×10 -2 and more preferably less than 4.0×10 -2 and even more preferably less than 2.0×10 -2 and still more preferably less than.
[0032] The toner of the first disclosure satisfies 45°C < Tg(°C) < 100°C for the glass transition temperature (Tg) specified from the temperature-tanδ curve obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. The glass transition temperature (Tg) is preferably 50°C or higher, more preferably 60°C or higher, and still more preferably 65°C or higher, among other things, from the viewpoint of suppressing a rapid decrease in elasticity at low temperatures and suppressing blocking. On the other hand, from the viewpoint of improving the low-temperature fixability by not allowing the softening start temperature of the toner to become too high, the glass transition temperature (Tg) is preferably 90°C or lower, more preferably 80°C or lower, and still more preferably 75°C or lower.
[0033] In addition, the toner of the first disclosure has a loss tangent (tan δ) at the glass transition temperature (Tg) of preferably less than 1.900, more preferably less than 1.870, and even more preferably 1.860 or less. By having the tan δ(Tg) be equal to or less than the upper limit, blocking during storage of the toner is easily suppressed, and storage stability is easily improved. The lower limit of the tan δ(Tg) is not particularly limited, but from the viewpoint of improving fixability, it is preferably 1.000 or more, and more preferably 1.100 or more.
[0034] The toner of the first disclosure has a loss tangent (tan δ) at 45° C., tan δ(45° C.), of preferably 0.300 or less, more preferably 0.200 or less, and even more preferably 0.150 or less. When the tan δ(45° C.) is equal to or less than the upper limit, blocking during storage of the toner is easily suppressed, and storage stability is easily improved. The lower limit of the tan δ (45° C.) is not particularly limited, but from the viewpoint of improving fixability, it is preferably more than 0.000, and more preferably 0.050 or more.
[0035] In addition, the toner of the first disclosure has a loss tangent (tan δ) at 100° C., tan δ(100° C.), which is preferably 0.600 or more, more preferably 0.700 or more, and even more preferably 0.800 or more, from the viewpoint of easily improving the low-temperature fixing property of the toner, while it is preferably 1.200 or less, more preferably 1.100 or less, and even more preferably 1.050 or less, from the viewpoint of easily suppressing deterioration of the storage stability of the toner.
[0036] In addition, the toner of the first disclosure has a loss tangent (tan δ) at 130° C., tan δ(130° C.), which is preferably 0.800 or more, more preferably 0.900 or more, and even more preferably 0.950 or more, from the viewpoint of easily improving the low-temperature fixing property of the toner, while it is preferably 2.000 or less, more preferably 1.500 or less, and even more preferably 1.280 or less, from the viewpoint of easily suppressing deterioration of the storage stability of the toner.
[0037] The toner of the first disclosure was subjected to a flow test at a pressure of 10.0 kgf / cm 2 The softening temperature (T 1 / 2 The softening temperature (T 1 / 2 When a toner having a viscoelasticity in a temperature-tan δ curve that satisfies the formula (I-1) and the formula (I-2) is used, the toner can improve low-temperature fixability and storage stability in a well-balanced manner. The softening temperature (T 1 / 2 From the viewpoint of improving storage stability, the softening temperature (T 1 / 2 ) is preferably 210° C. or less, and more preferably 200° C. or less. The softening temperature (T 1 / 2 The softening temperature (T 1 / 2 ) tends to increase. In addition, the softening temperature (T 1 / 2 In addition, by using a colorant that easily increases the viscosity of the toner as described below, the toner of the first disclosure has a tendency to have a high softening temperature (T 1 / 2 ) is likely to be within the above range.
[0038] The flow tester was used at a pressure of 10.0 kgf / cm 2The softening temperature (T 1 / 2 The softening temperature (T) can be determined from a flow curve (piston stroke-temperature) measured under the following measurement conditions using a Shimadzu flow tester (product name: CFT-500C). Specifically, in the flow curve, half the difference between the piston stroke at the end of outflow and the minimum value of the piston stroke is calculated, and the temperature at the position where the calculated value and the minimum value are added is defined as the softening temperature (T 1 / 2 ) can be obtained. (Measurement conditions) Starting temperature: 35℃ Heating rate: 3℃ / min Preheat time: 5 minutes Cylinder pressure: 10.0kgf / cm 2 (10kg method) Die hole diameter: 0.5mm Die length: 1.0mm Sample input amount: 1.0~1.3g
[0039] I-2. Manufacturing method of colored resin particles In general, methods for producing colored resin particles are roughly divided into dry methods such as pulverization methods, and wet methods such as emulsion polymerization aggregation methods, suspension polymerization methods, and dissolution suspension methods, with the wet methods being preferred because they are more likely to produce toners with excellent printing characteristics such as image reproducibility. Among the wet methods, the emulsion polymerization aggregation methods and polymerization methods such as suspension polymerization methods are more preferred because they are more likely to produce toners with a relatively small particle size distribution on the order of microns, and among the polymerization methods, suspension polymerization is more preferred.
[0040] The emulsion polymerization aggregation method is a method of producing colored resin particles by polymerizing an emulsified polymerizable monomer to obtain a resin fine particle emulsion, and aggregating the resin fine particle emulsion with a colorant dispersion liquid or the like. The dissolution suspension method is a method of producing colored resin particles by forming droplets of a solution in which toner components such as a binder resin and a colorant are dissolved or dispersed in an organic solvent in an aqueous medium, and removing the organic solvent, and each of these methods can be known.
[0041] The colored resin particles used in the toner of the first present disclosure can be produced by employing a wet method or a dry method, but a wet method is preferred, and among the wet methods, a suspension polymerization method is particularly preferred, and the colored resin particles can be produced by the following process.
[0042] (A) Suspension polymerization method (A-1) Preparation of polymerizable monomer composition First, a polymerizable monomer composition is prepared by mixing a polymerizable monomer, a colorant, a softener, a charge control agent, and, if necessary, other additives such as a molecular weight modifier, etc. The mixing for preparing the polymerizable monomer composition is performed, for example, using a media type dispersing machine.
[0043] In the present disclosure, the polymerizable monomer refers to a monomer having a polymerizable functional group, and the polymerizable monomer is polymerized to become a binder resin. It is preferable to use a monovinyl monomer as the main component of the polymerizable monomer. Examples of the monovinyl monomer include styrene; styrene derivatives such as vinyl toluene and α-methylstyrene; acrylic acid and methacrylic acid; acrylic acid esters such as methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, and dimethylaminoethyl acrylate; methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, and dimethylaminoethyl methacrylate; nitrile compounds such as acrylonitrile and methacrylonitrile; amide compounds such as acrylamide and methacrylamide; and olefins such as ethylene, propylene, and butylene. These monovinyl monomers can be used alone or in combination of two or more. Among these, the toner temperature-tan δ curve is likely to satisfy the formula (I-1) and the formula (I-2), and the softening temperature (T 1 / 2) is likely to be in the preferred range, the polymerizable monomer preferably contains at least one monovinyl monomer selected from the group consisting of styrene, a styrene derivative, an acrylic acid ester, and a methacrylic acid ester, more preferably contains at least one monovinyl monomer selected from the group consisting of styrene, an acrylic acid ester, and a methacrylic acid ester, and even more preferably contains styrene and at least one selected from the group consisting of an acrylic acid ester and a methacrylic acid ester. In addition, the temperature-tan δ curve of the toner is likely to satisfy the formula (I-1) and the formula (I-2), and the softening temperature (T 1 / 2 ) is likely to fall within the above-mentioned preferred range, the acrylic ester is preferably at least one selected from the group consisting of n-butyl acrylate, propyl acrylate, and 2-ethylhexyl acrylate, and the methacrylic ester is preferably at least one selected from the group consisting of n-butyl methacrylate, propyl methacrylate, and 2-ethylhexyl methacrylate.
[0044] The content of styrene in 100 parts by mass of the total of the monovinyl monomers is preferably 60 parts by mass or more and 90 parts by mass or less, more preferably 65 parts by mass or more and 85 parts by mass or less, and further preferably 70 parts by mass or more and 80 parts by mass or less. 1 / 2 ) becomes higher, and the glass transition temperature (Tg) of the toner tends to become higher.
[0045] In addition, the temperature-tan δ curve of the toner is likely to satisfy the formula (I-1) and the formula (I-2), and the softening temperature (T 1 / 2Since the mass ratio of the styrene to the total of the acrylic acid ester and the methacrylic acid ester (styrene:(meth)acrylic acid ester) is likely to be in the preferred range, the monovinyl monomer contains styrene and at least one selected from the group consisting of an acrylic acid ester and a methacrylic acid ester, and the mass ratio of the styrene to the total of the acrylic acid ester and the methacrylic acid ester (styrene:(meth)acrylic acid ester) is preferably within a range of 50:50 to 90:10, more preferably within a range of 60:40 to 80:20, and particularly preferably within a range of 70:30 to 75:25.
[0046] When the polymerizable monomer contains a polymerizable monomer other than the monovinyl monomer, the content of the monovinyl monomer is appropriately adjusted so that the temperature-tan δ curve of the toner satisfies the formula (I-1) and the formula (I-2). Although not particularly limited, the total amount of the monovinyl monomer is preferably 90 parts by mass or more, and more preferably 95 parts by mass or more, per 100 parts by mass of the total amount of the polymerizable monomer.
[0047] In the toner of the first disclosure, the temperature-tan δ curve is likely to satisfy the formula (I-1) and the formula (I-2), and the softening temperature (T 1 / 2 ) is likely to fall within the above-mentioned preferred range, it is preferable to use any crosslinkable polymerizable monomer together with the monovinyl monomer. The crosslinkable polymerizable monomer refers to a monomer having two or more polymerizable functional groups. Examples of the crosslinkable polymerizable monomer include aromatic divinyl compounds such as divinylbenzene, divinylnaphthalene, and derivatives thereof; ester compounds in which two or more carboxylic acids are ester-bonded to an alcohol having two or more hydroxyl groups, such as ethylene glycol dimethacrylate and diethylene glycol dimethacrylate; other divinyl compounds such as N,N-divinylaniline and divinyl ether; and compounds having three or more vinyl groups; and among these, at least one selected from the group consisting of divinylbenzene, divinylnaphthalene, and derivatives thereof is preferable. These crosslinkable polymerizable monomers can be used alone or in combination of two or more. In the present disclosure, the crosslinkable polymerizable monomer is used in an amount of usually 0.10 to 2.00 parts by mass, preferably 0.50 to 1.50 parts by mass, more preferably 0.65 to 1.00 parts by mass, and particularly preferably 0.70 to 0.90 parts by mass, relative to 100 parts by mass of the monovinyl monomer. As the content of the crosslinkable polymerizable monomer increases, the weight average molecular weight of the polymer of the polymerizable monomer tends to increase, and the softening temperature (T 1 / 2 In addition, as the content of the crosslinkable polymerizable monomer increases, tan δ at 100° C. and tan δ at 130° C. tend to decrease in the temperature-tan δ curve of the toner, and the value of (tan δ(130° C.)-tan δ(100° C.)) / 30 shown in the above formula (I-2) tends to decrease.
[0048] The polymerizable monomer may contain a macromonomer together with the monovinyl monomer. By including a macromonomer in the polymerizable monomer, the balance between the storage stability and low-temperature fixability of the toner can be improved. Examples of the macromonomer include a reactive oligomer and polymer having a polymerizable carbon-carbon unsaturated double bond at the end of the molecular chain, and having a number average molecular weight of usually 1,000 to 30,000. Examples of the macromonomer include a styrene macromonomer, a styrene-acrylonitrile macromonomer, a polyacrylic acid ester macromonomer, and a polymethacrylic acid ester macromonomer. Among them, at least one selected from a polyacrylic acid ester macromonomer and a polymethacrylic acid ester macromonomer can be preferably used from the viewpoint of easy control of the glass transition temperature (Tg) of the toner. Examples of the acrylic acid ester used in the polyacrylic acid ester macromonomer include the same acrylic acid ester usable as the monovinyl monomer, and examples of the methacrylic acid ester used in the polymethacrylic acid ester macromonomer include the same methacrylic acid ester usable as the monovinyl monomer. As the macromonomer, it is preferable to appropriately select and use a macromonomer that, when contained in the polymerizable monomer, gives a binder resin with a higher glass transition temperature (Tg) than when not contained, since this makes it easier to bring the glass transition temperature (Tg) of the toner into the preferred range. The macromonomer may be a commercially available product. Examples of the commercially available macromonomer include macromonomer series AA-6, AS-6, AN-6S, AB-6, and AW-6S manufactured by Toagosei Co., Ltd. The macromonomers can be used alone or in combination of two or more. When the polymerizable monomer contains the macromonomer, the content of the macromonomer is appropriately adjusted so that the temperature-tan δ curve of the toner satisfies the formula (I-1) and the formula (I-2), and is not particularly limited, but is preferably used in a ratio of 0.03 to 5 parts by mass, more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the monovinyl monomer.
[0049] The content of the polymerizable monomers is appropriately adjusted so that the temperature-tan δ curve of the toner satisfies the formula (I-1) and the formula (I-2), and is not particularly limited, but the total content of the polymerizable monomers is preferably 60 to 95 parts by mass, more preferably 65 to 90 parts by mass, and even more preferably 70 to 90 parts by mass, relative to 100 parts by mass of the total solid content contained in the polymerizable monomer composition. In the present disclosure, the solid content refers to all components other than the solvent, and liquid monomers and the like are also included in the solid content.
[0050] The colorant contained in the toner of the first disclosure can be appropriately selected from colorants used in conventional toners, and is not particularly limited, but a colorant that easily increases the viscosity of the toner can be suitably used. Here, the colorant that easily increases the viscosity of the toner is a colorant in which the intermolecular force generated between the toner and the binder resin contained in the toner and the intermolecular force generated between the colorants themselves are relatively high. The colorant that easily increases the viscosity of the toner is typically a colorant that can form a hydrogen bond with the binder resin. For example, when the toner contains a polymer of a polymerizable monomer containing styrene and at least one monovinyl monomer selected from the group consisting of acrylic acid esters and methacrylic acid esters as the binder resin, if the colorant is a colorant having at least one functional group selected from the group consisting of a hydroxyl group, an aldehyde group, a carbonyl group, a carboxyl group, an ester group, an ether group, an amino group, an amide group, and a cyano group, the colorant is likely to form a hydrogen bond with a monomer unit derived from the acrylic acid ester or methacrylic acid ester of the polymer contained as the binder resin. Furthermore, the colorant having the functional group is more likely to increase the viscosity of the toner as the amount of the functional group contained in one molecule increases. Furthermore, the smaller the particle size of the colorant contained in the toner, the stronger the intermolecular forces generated between the colorant and the binder resin and between the colorants themselves, and therefore the greater the viscosity of the toner tends to increase. By using such a colorant that easily increases the viscosity of the toner, the softening temperature (T 1 / 2In addition, by using such a colorant that easily increases the viscosity of the toner, the reaction rate of the polymerizable monomer increases in the polymerization step described below, and the weight average molecular weight of the polymer of the polymerizable monomer increases. This also makes it possible to increase the softening temperature (T 1 / 2 ) tends to be in the preferred range. Furthermore, when a colorant that easily increases the viscosity of the toner is used, the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the above formula (I-2) tends to be smaller in the toner temperature-tan δ curve.
[0051] As the colorant that easily increases the viscosity of the toner as described above, for example, a colorant that has the same type and content as the polymerizable monomer composition used in the production of the toner, and a mixture of the colorant, polymerizable monomer, and molecular weight modifier, has a viscosity of preferably 200 to 1500 mPa s, and more preferably 240 to 1000 mPa s. In the toner of the first disclosure, it is preferable to select the type and content of the colorant and the type and content of the polymerizable monomer so that the viscosity of the mixture falls within the above range. By having the viscosity of the mixture fall within the above range, the temperature-tan δ curve of the toner easily satisfies the formula (I-1) and the formula (I-2), and the softening temperature (T 1 / 2 ) is likely to be in the above-mentioned preferred range, the balance between low-temperature fixability and storage stability is likely to be good. The viscosity of the mixture can be set within the above range, for example, by using a colorant that easily increases the viscosity of the toner and a polymerizable monomer that includes styrene and at least one monovinyl monomer selected from the group consisting of acrylic acid esters and methacrylic acid esters in combination. The smaller the particle size of the colorant, the higher the viscosity of the mixture tends to be.
[0052] The colorant contained in the toner of the first disclosure can be appropriately selected from colorants used in conventional toners and is not particularly limited. When producing a color toner, black, cyan, yellow, and magenta colorants can be used. As the black colorant, for example, carbon black, titanium black, and magnetic powders such as zinc iron oxide and nickel iron oxide can be used. Examples of cyan colorants that can be used include phthalocyanine pigments such as copper phthalocyanine pigments and derivatives thereof, cyan pigments such as anthraquinone pigments, and cyan dyes. Specific examples include CI Pigment Blue 2, 3, 6, 15, 15:1, 15:2, 15:3, 15:4, 16, 17:1, 60; CI Solvent Blue 70, etc. Examples of the yellow colorant that can be used include azo pigments such as monoazo pigments and disazo pigments, condensed polycyclic pigments, yellow dyes, etc. Specific examples include CI Pigment Yellow 3, 12, 13, 14, 15, 17, 62, 65, 73, 74, 83, 93, 97, 120, 138, 155, 180, 181, 185, 186, 213, 214; CI Solvent Yellow 98, 162, etc. Examples of the magenta colorant that can be used include azo pigments such as monoazo pigments and disazo pigments, magenta pigments such as condensed polycyclic pigments such as quinacridone pigments, and magenta dyes.Specific examples of the magenta colorant that can be used include CI Pigment Red 31, 48, 57:1, 58, 60, 63, 64, 68, 81, 83, 87, 88, 89, 90, 112, 114, 122, 123, 144, 146, 149, 150, 163, 170, 184, 185, 187, 202, 206, 207, 209, 237, 238, 251, 254, 255, 269; CI Pigment Violet 19; CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 4 9, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28, etc. The colorants may be used alone or in combination of two or more. The colorant contained in the toner of the first disclosure is a colorant having a temperature-tan δ curve that is likely to satisfy the formula (I-1) and the formula (I-2), and has a softening temperature (T 1 / 2 ) is likely to fall within the above-mentioned preferred range, preferably a yellow colorant made of a yellow pigment is used, and among them, from the viewpoint of easily increasing the viscosity of the toner as described above, more preferably a yellow colorant made of a yellow pigment not containing a chlorine atom is used, even more preferably a yellow colorant made of an azo yellow pigment not containing a chlorine atom is used, and even more preferably a yellow colorant made of a disazo yellow pigment not containing a chlorine atom is used. Specifically, for example, at least one selected from CI Pigment Yellow 155 and CI Pigment Yellow 93 is preferred, and CI Pigment Yellow 155 is more preferred.
[0053] The content of the colorant is usually 1 to 20 parts by mass, preferably 5 to 15 parts by mass, and more preferably 7 to 13 parts by mass, based on 100 parts by mass of the total amount of the polymerizable monomer. When the content of the colorant is within the above range, the temperature-tan δ curve of the toner easily satisfies the above formulas (I-1) and (I-2), and the softening temperature (T 1 / 2 ) tends to be in the preferred range.
[0054] The polymerizable monomer composition contains a softener. By containing a softener, the releasability of the toner from the fixing roll during fixing can be improved. As the softener, any softener generally used as a toner softener or release agent can be used without any particular limitation. For example, low molecular weight polyolefin wax and modified wax thereof; petroleum wax such as paraffin; mineral wax such as ozokerite; synthetic wax such as Fischer-Tropsch wax; ester wax such as dipentaerythritol ester and carnauba; etc. can be mentioned. Among them, ester wax is preferred from the viewpoint of adjusting the viscoelasticity of the toner and improving the balance between the storage stability and low-temperature fixability of the toner, and is more preferred than synthetic ester wax obtained by esterifying alcohol and carboxylic acid, and more preferred is polyfunctional ester wax obtained by esterifying polyhydric alcohol and monocarboxylic acid. As the polyfunctional ester wax, for example, at least one selected from the group consisting of pentaerythritol ester compounds, glycerin ester compounds and dipentaerythritol ester compounds can be preferably used. Such preferred polyfunctional ester waxes include, for example, pentaerythritol ester compounds such as pentaerythritol tetrapalmitate, pentaerythritol tetrabehenate, and pentaerythritol tetrastearate; glycerin ester compounds such as hexaglycerin tetrabehenate tetrapalmitate, hexaglycerin octabehenate, pentaglycerin heptabehenate, tetraglycerin hexabehenate, triglycerin pentabehenate, diglycerin tetrabehenate, and glycerin tribehenate; dipentaerythritol ester compounds such as dipentaerythritol hexamyristate and dipentaerythritol hexapalmitate; and the like.
[0055] The weight average molecular weight Mw of the softener is not particularly limited, but is preferably within a range of 400 to 3500, and more preferably 500 to 3000. The larger the weight average molecular weight Mw of the softener, the higher the softening temperature (T 1 / 2 ) tends to be higher. The weight average molecular weight Mw of the softener can be measured by the same method as the weight average molecular weight Mw of the polymer described later. In addition, in the case of ester wax, it can be extracted with a solvent, decomposed into alcohol and carboxylic acid by hydrolysis, and the composition analysis can be performed to calculate the molecular weight from the structural formula. The weight average molecular weight Mw of the ester wax is the same as the molecular weight calculated from the structural formula.
[0056] In addition, from the viewpoint of adjusting the viscoelasticity of the toner and improving the balance between the storage stability and low-temperature fixability of the toner, the melting point of the softener is preferably within a range of 50 to 90°C, more preferably within a range of 60 to 85°C, and even more preferably within a range of 70 to 80°C. The content of the softener is not particularly limited, but from the viewpoint of adjusting the viscoelasticity of the toner and improving the balance between the storage stability and low-temperature fixability of the toner, the softener is preferably used in a ratio of 1 to 30 parts by mass, more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the monovinyl monomer. The softening agents may be used alone or in combination of two or more.
[0057] The polymerizable monomer composition contains a positively or negatively chargeable charge control agent, which can improve the chargeability of the toner. The charge control agent is not particularly limited as long as it is one that is generally used as a charge control agent for toners. Among the charge control agents, a positively or negatively charged charge control resin is preferred because it has high compatibility with polymerizable monomers and can impart stable chargeability (charge stability) to toner particles. Furthermore, from the viewpoint of obtaining a positively charged toner, a positively charged charge control resin is more preferably used.
[0058] As the positively or negatively charged charge control resin, a functional group-containing copolymer can be used. As the positively charged charge control resin, for example, a functional group-containing copolymer containing a structural unit containing a functional group such as an amino group, a quaternary ammonium group, or a quaternary ammonium salt-containing group can be used, and examples thereof include polyamine resins, quaternary ammonium group-containing copolymers, and quaternary ammonium base-containing copolymers. As the negatively charged charge control resin, for example, a functional group-containing copolymer containing a structural unit containing a functional group such as a sulfonic acid group, a sulfonate salt-containing group, a carboxylic acid group, or a carboxylate salt-containing group can be used, and examples thereof include sulfonic acid group-containing copolymers, sulfonate salt salt-containing copolymers, carboxylic acid group-containing copolymers, and carboxylate salt salt-containing copolymers. The functional group-containing copolymer used as the positively or negatively charged charge control resin is preferably one in which the proportion of functional group-containing structural units in the functional group-containing copolymer is 10% by mass or less, more preferably 9% by mass or less, from the viewpoint of easily satisfying the formula (I-1) and the formula (I-2) in the temperature-tan δ curve of the toner. On the other hand, from the viewpoint of improving the charge stability and storage stability of the toner, the proportion of functional group-containing structural units in the functional group-containing copolymer is preferably 0.5% by mass or more. It is presumed that the charge control resin contains a sufficient amount of functional groups, so that the charge control resin is easily localized near the surface of the colored resin particles, and the charge control resin functions like a shell of the colored resin particles, thereby improving the storage stability of the toner.
[0059] The functional group-containing copolymer used as the positively or negatively charged charge control resin is preferably a styrene-acrylic resin, since it has high compatibility with the polymerizable monomer and is likely to satisfy the formula (I-1) and the formula (I-2) in the temperature-tan δ curve of the toner.
[0060] The functional group-containing copolymer used as the positively or negatively charged charge control resin preferably has a glass transition temperature (Tg) of 50 to 110° C., more preferably 60 to 100° C. When the glass transition temperature (Tg) of the functional group-containing copolymer is within the above range, the toner temperature-tan δ curve is likely to satisfy the formula (I-1) and the formula (I-2), and the storage stability of the toner can be improved. The functional group-containing copolymer is likely to be localized near the surface of the colored resin particles and can function like a shell. Therefore, when the Tg of the functional group-containing copolymer is within the above range, the storage stability of the toner is presumably improved due to the sufficiently high Tg. The glass transition temperature (Tg) of the functional group-containing copolymer is measured by the same method as that for the glass transition temperature (Tg) of the toner described above.
[0061] The functional group-containing copolymer used as the positively or negatively charged charge control resin preferably has a weight average molecular weight Mw of 5,000 to 30,000, and more preferably 10,000 to 25,000.
[0062] Examples of the charge control agent other than the positively chargeable charge control resin include nigrosine dyes, quaternary ammonium salts, triaminotriphenylmethane compounds, and imidazole compounds. Examples of the charge control agent other than the negatively chargeable charge control resin include azo dyes containing metals such as Cr, Co, Al, and Fe, metal salicylate compounds, and metal alkylsalicylate compounds. The charge control agents can be used alone or in combination of two or more.
[0063] In the present disclosure, the charge control agent is usually used in an amount of 0.01 to 10 parts by mass, preferably 0.03 to 8 parts by mass, based on 100 parts by mass of the monovinyl monomer. When the content of the charge control agent is 0.01 parts by mass or more, the occurrence of fog can be suppressed, whereas when the amount of the charge control agent added is 10 parts by mass or less, print smearing can be suppressed.
[0064] The polymerizable monomer composition preferably further contains a molecular weight modifier. The molecular weight regulator is not particularly limited as long as it is one that is generally used as a molecular weight regulator for toners, and examples thereof include mercaptans such as t-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, and 2,2,4,6,6-pentamethylheptane-4-thiol; thiuram disulfides such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, tetrabutylthiuram disulfide, N,N'-dimethyl-N,N'-diphenylthiuram disulfide, and N,N'-dioctadecyl-N,N'-diisopropylthiuram disulfide; etc. These molecular weight regulators may be used alone or in combination of two or more kinds.
[0065] In the first toner of the present disclosure, the temperature-tan δ curve of the toner is likely to satisfy the formula (I-1) and the formula (I-2), and the softening temperature (T 1 / 2 Since the weight average molecular weight Mw of the polymer contained in the binder resin is likely to be in the above-mentioned preferred range, it is preferable to adjust the content of the molecular weight modifier so that the weight average molecular weight Mw of the polymer contained in the binder resin is in the preferred range described below. The molecular weight modifier is used in a ratio of preferably 1.0 to 3.0 parts by mass, more preferably 1.1 to 2.0 parts by mass, per 100 parts by mass of the monovinyl monomer. Note that the greater the content of the molecular weight modifier, the smaller the weight average molecular weight of the polymer contained in the binder resin tends to be, and the softening temperature (T 1 / 2 ) tends to be lower. In addition, the higher the content of the molecular weight modifier, the higher the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) shown in the above formula (I-1) and the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the above formula (I-2) in the temperature-tan δ curve of the toner tend to be. In addition, the higher the content of the molecular weight modifier, the lower the glass transition temperature (Tg) of the toner tends to be, and the tan at Tg, tan δ at 100°C, and tan δ at 130°C tend to be increased.
[0066] (A-2) Suspension step for obtaining a suspension (droplet formation step) Next, the polymerizable monomer composition is dispersed in an aqueous medium containing a dispersion stabilizer, a polymerization initiator is added, and then droplets of the polymerizable monomer composition are formed. The polymerization initiator may be added before droplets are formed after the polymerizable monomer composition is dispersed in the aqueous medium as described above, or may be added to the polymerizable monomer composition before it is dispersed in the aqueous medium. The method of forming droplets is not particularly limited, but may be carried out using a device capable of strong stirring, such as an (in-line type) emulsifying disperser (manufactured by Pacific Machinery Works, product name: Milder) or a high-speed emulsifying disperser (manufactured by Primix Corporation, product name: TK Homo Mixer MARK II type).
[0067] Examples of the polymerization initiator include persulfates such as potassium persulfate and ammonium persulfate; azo compounds such as 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobisisobutyronitrile; and organic peroxides such as di-t-butyl peroxide, benzoyl peroxide, t-butylperoxy-2-ethylhexanoate, t-butylperoxy-2-ethylbutanoate, t-hexylperoxy-2-ethylbutanoate, diisopropylperoxydicarbonate, di-t-butylperoxyisophthalate, and t-butylperoxyisobutyrate. Among these, it is preferable to use organic peroxides because they can reduce the amount of residual polymerizable monomers and have excellent print durability. Among the organic peroxides, peroxyesters are preferable because they have good initiator efficiency and can reduce the amount of residual polymerizable monomers, and non-aromatic peroxyesters, i.e., peroxyesters without an aromatic ring, are more preferable. These polymerization initiators can be used alone or in combination of two or more.
[0068] The amount of the polymerization initiator used in the polymerization reaction of the polymerizable monomer composition is preferably 0.1 to 20 parts by mass, more preferably 0.3 to 15 parts by mass, and particularly preferably 1 to 10 parts by mass, based on 100 parts by mass of the monovinyl monomer.
[0069] In the present disclosure, an aqueous medium refers to a medium containing water as a main component. In the present disclosure, it is preferable that the aqueous medium contains a dispersion stabilizer. Examples of the dispersion stabilizer include inorganic compounds such as sulfates such as barium sulfate and calcium sulfate; carbonates such as barium carbonate, calcium carbonate, and magnesium carbonate; phosphates such as calcium phosphate; metal oxides such as aluminum oxide and titanium oxide; metal hydroxides such as aluminum hydroxide, magnesium hydroxide, and ferric hydroxide; and organic compounds such as water-soluble polymers such as polyvinyl alcohol, methyl cellulose, and gelatin; anionic surfactants; nonionic surfactants; and amphoteric surfactants. These dispersion stabilizers can be used alone or in combination of two or more.
[0070] Among the above dispersion stabilizers, inorganic compounds are preferred, and as the aqueous medium containing the dispersion stabilizer, colloidal metal hydroxides that are poorly water-soluble are particularly preferred. By using an inorganic compound, particularly a colloidal metal hydroxide that is poorly water-soluble, the particle size distribution of the colored resin particles can be narrowed, and the amount of the dispersion stabilizer remaining after washing can be reduced, so that the obtained polymerized toner can reproduce images clearly and does not deteriorate the environmental stability.
[0071] (A-3) Polymerization process After forming droplets of the polymerizable monomer composition as described above in (A-2), the polymerizable monomer composition is subjected to a polymerization reaction in the presence of a polymerization initiator to form colored resin particles. That is, the aqueous dispersion medium in which the droplets of the polymerizable monomer composition are dispersed is heated to initiate polymerization, and an aqueous dispersion of colored resin particles is formed. The heating conditions are preferably adjusted so that the weight average molecular weight Mw of the polymer of the polymerizable monomer falls within the preferred range described below, and are not particularly limited, but the heating temperature is preferably 50° C. or higher, and more preferably 60 to 95° C. The heating time is preferably 1 to 20 hours, and more preferably 2 to 15 hours.
[0072] The colored resin particles may be used as a toner as is or with the addition of an external additive, but it is preferable to use the colored resin particles as the core layer of so-called core-shell type (or "capsule type") colored resin particles. The core-shell type colored resin particles have a structure in which the outside of the core layer is covered with a shell layer formed of a material different from the core layer. By covering the core layer made of a material having a low softening point with a material having a higher softening point, it is easy to satisfy the above formula (I-1) and the above formula (I-2) in the temperature-tan δ curve, and the low-temperature fixability and storage stability of the toner can be improved in a well-balanced manner.
[0073] The method for producing the core-shell type colored resin particles using the above-mentioned colored resin particles is not particularly limited, and the core-shell type colored resin particles can be produced by a conventionally known method. In terms of production efficiency, the in situ polymerization method and the phase separation method are preferred.
[0074] A method for producing core-shell type colored resin particles by in situ polymerization will be described below. A polymerizable monomer for forming a shell layer (polymerizable monomer for shell) and a polymerization initiator are added to an aqueous medium in which colored resin particles are dispersed, and polymerized to obtain core-shell type colored resin particles.
[0075] As the polymerizable monomer for the shell, the same polymerizable monomers as those described above can be used. Among them, it is preferable to use monomers such as styrene, acrylonitrile, and methyl methacrylate, which can give a polymer with a Tg exceeding 80° C., either alone or in combination of two or more kinds.
[0076] Examples of the polymerization initiator used for polymerization of the shell polymerizable monomer include water-soluble polymerization initiators such as metal persulfates such as potassium persulfate and ammonium persulfate; and azo initiators such as 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide) and 2,2'-azobis-(2-methyl-N-(1,1-bis(hydroxymethyl)2-hydroxyethyl)propionamide). These can be used alone or in combination of two or more. The amount of the polymerization initiator is preferably 0.1 to 30 parts by mass, more preferably 1 to 20 parts by mass, based on 100 parts by mass of the shell polymerizable monomer.
[0077] The polymerization temperature for the shell layer is preferably 50° C. or higher, and more preferably 60 to 95° C. The polymerization reaction time is preferably 1 to 20 hours, and more preferably 2 to 15 hours.
[0078] (A-4) Washing, filtering, dehydrating, and drying steps After the polymerization is completed, the aqueous dispersion of colored resin particles obtained by polymerization is preferably filtered, washed to remove the dispersion stabilizer, dehydrated, and dried in a conventional manner, and if necessary, the operations are repeated several times.
[0079] As for the above-mentioned washing method, when an inorganic compound is used as a dispersion stabilizer, it is preferable to add an acid or alkali to the aqueous dispersion of the colored resin particles to dissolve and remove the dispersion stabilizer in water. When a colloid of a poorly water-soluble inorganic hydroxide is used as the dispersion stabilizer, it is preferable to add an acid to adjust the pH of the aqueous dispersion of the colored resin particles to 6.5 or less. As the acid to be added, inorganic acids such as sulfuric acid, hydrochloric acid, and nitric acid, and organic acids such as formic acid and acetic acid can be used, but sulfuric acid is particularly preferable because of its high removal efficiency and its small burden on the production equipment.
[0080] The dehydration and filtration methods can be any of various known methods, and are not particularly limited. For example, centrifugal filtration, vacuum filtration, pressure filtration, etc. can be mentioned. The drying method is also not particularly limited, and various methods can be used.
[0081] (B) Crushing method When the colored resin particles are produced by the pulverization method, the process is, for example, as follows. First, the binder resin, colorant, softener, charge control agent, and other additives added as necessary are mixed using a mixer such as a ball mill, V-type mixer, FM mixer (trade name), high-speed dissolver, internal mixer, or Fallberg. Next, the mixture obtained above is kneaded while heating using a pressure kneader, a twin-screw extrusion kneader, a roller, or the like. The kneaded product obtained is coarsely pulverized using a pulverizer such as a hammer mill, a cutter mill, or a roller mill. Furthermore, the product is finely pulverized using a pulverizer such as a jet mill or a high-speed rotary pulverizer, and then classified into desired particle sizes using a classifier such as an air classifier or an airflow classifier to obtain colored resin particles by the pulverization method.
[0082] The binder resin, colorant, softener, and charge control agent used in the pulverization method may be the same as those listed in the suspension polymerization method (A). The colored resin particles obtained by the pulverization method may be used in a method such as in situ polymerization to produce core-shell type colored resin particles, in the same manner as the colored resin particles obtained by the suspension polymerization method (A).
[0083] As the binder resin, resins that have been widely used in toners can also be used. Specific examples of the binder resin used in the pulverization method include polystyrene, styrene-butyl acrylate copolymers, polyester resins, and epoxy resins.
[0084] I-3. Colored resin particles The colored resin particles can be obtained by the above-mentioned production method such as (A) the suspension polymerization method or (B) the pulverization method. The colored resin particles contained in the toner of the first aspect of the present disclosure will be described below. The colored resin particles described below include both core-shell type and non-core-shell type particles.
[0085] The colored resin particles used in the toner of the first aspect of the present disclosure contain a binder resin, a colorant, a softener, and a charge control agent, and may further contain other additives as necessary.
[0086] The binder resin contained in the colored resin particles may be, for example, a polymer obtained by polymerizing the polymerizable monomers listed in the suspension polymerization method (A) above. In the present disclosure, the polymer may be either a homopolymer or a copolymer. The preferred polymerizable monomers from which each structural unit of the polymer is derived are the same as the preferred polymerizable monomers described in the suspension polymerization method (A) above. The toner is likely to satisfy the formulas (I-1) and (I-2) in the temperature-tan δ curve, and the softening temperature (T 1 / 2 ) is likely to fall within the above-mentioned preferred range, and the low-temperature fixability and storage stability of the toner are likely to be improved in a well-balanced manner. Therefore, the binder resin contained in the colored resin particles preferably contains a polymer of one or more polymerizable monomers including at least one monovinyl monomer selected from the group consisting of styrene, acrylic acid esters, and methacrylic acid esters, more preferably contains a polymer of one or more polymerizable monomers including styrene and at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters, and even more preferably contains a polymer of a polymerizable monomer including styrene, at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters, and at least one selected from the group consisting of divinylbenzene, divinylnaphthalene, and derivatives thereof. The structure and ratio of each structural unit in the total structural units of the polymer can be determined from the amount of each structural unit used when synthesizing the polymer. 1 It can be calculated from the integral value obtained by H-NMR measurement.
[0087] The weight average molecular weight Mw of the polymer contained in the binder resin is such that the toner easily satisfies the above formula (I-1) and the above formula (I-2) in the temperature-tan δ curve, and the softening temperature (T 1 / 2 ) is likely to fall within the above-mentioned preferred range, and the low-temperature fixability and storage stability of the toner are likely to be improved in a well-balanced manner.5 Above 1.00 x 10 6 Among these, the lower limit of the weight average molecular weight Mw is more preferably 2.00×10 or less from the viewpoint of improving the storage stability of the toner. 5 More preferably, 3.00×10 5 More preferably, 3.1×10 5 On the other hand, the upper limit of the weight average molecular weight Mw is more preferably 7.00×10 5 Less than 5.50×10, more preferably 5 More preferably, 5.00×10 5 The polymer contained in the binder resin is typically a polymer of the above-mentioned polymerizable monomer. As the weight average molecular weight Mw of the polymer decreases, the toner Tg decreases and tan δ(Tg) increases, so the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) shown in the formula (I-1) tends to increase. As the weight average molecular weight Mw of the polymer decreases, both tan δ(100°C) and tan δ(130°C) of the toner tend to increase, but since the increase in tan δ(130°C) is more likely to be greater, the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (I-2) tends to increase. As the weight average molecular weight Mw of the polymer increases, the softening temperature (T 1 / 2 In addition, by setting the weight average molecular weight Mw of the polymer to be equal to or less than the upper limit, deterioration of storage stability is likely to be suppressed. In the present disclosure, the weight average molecular weight Mw of the polymer can be determined by polystyrene conversion using GPC. As a sample for GPC measurement, a polymer to be measured is usually dissolved in tetrahydrofuran (THF). When measuring the weight average molecular weight Mw of the polymer contained in the binder resin, a toner dissolved in tetrahydrofuran (THF) is used as a sample for GPC measurement, and the weight average molecular weight Mw of the polymer contained as the binder resin can be determined using data obtained by subtracting from the measurement results the peaks previously measured for polymers other than the polymer contained as the binder resin, i.e., the charge control resin and the softener, etc.
[0088] The binder resin contained in the colored resin particles is typically a polymer of the polymerizable monomer, but may contain a small amount of polyester resin, epoxy resin, or the like that has been widely used as a binder resin for toner, or unreacted polymerizable monomer, as long as the toner satisfies the formula (I-1) and the formula (I-2) in the temperature-tan δ curve. Among them, the content of the polyester resin contained in 100 parts by mass of the binder resin is preferably 5 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.1 parts by mass or less, and it is particularly preferable that the binder resin does not contain a polyester resin. By having the content of the polyester resin be equal to or less than the upper limit, the environmental stability of the toner can be improved, and in particular, the change in the charge of the toner due to the change in humidity can be suppressed. In addition, when the binder resin contains a resin other than the polymer of the polymerizable monomer, the content of the polymer of the polymerizable monomer in 100 parts by mass of the binder resin is preferably 95 parts by mass or more, more preferably 97 parts by mass or more, and even more preferably 99 parts by mass or more, from the viewpoint that the temperature-tan δ curve of the toner is likely to satisfy the formula (I-1) and the formula (I-2). In the present disclosure, the molecular weight modifier used in the polymerization reaction is included in the binder resin.
[0089] The total content of the binder resin is preferably 60 to 95 parts by mass, more preferably 65 to 90 parts by mass, and even more preferably 70 to 85 parts by mass, relative to 100 parts by mass of the total solid content contained in the colored resin particles, from the viewpoint that the toner easily satisfies the formula (I-1) and the formula (I-2) in the temperature-tan δ curve. Further, the content of structural units derived from styrene in the total amount (100% by mass) of the binder resin is preferably 60 to 90% by mass, more preferably 65 to 85% by mass, and further preferably 70 to 80% by mass. In addition, the content of the constitutional unit derived from the crosslinkable polymerizable monomer in the total amount of the binder resin (100% by mass) is preferably 0.10 to 2.00% by mass, more preferably 0.50 to 1.50% by mass, and even more preferably 0.65 to 1.00% by mass.
[0090] The colorant, softener and charge control agent contained in the colored resin particles are the same as those mentioned in the above suspension polymerization method (A). The content of the colorant contained in the colored resin particles is appropriately adjusted depending on the type of colorant so that a desired color is obtained and the toner satisfies the formula (I-1) and the formula (I-2) in the temperature-tan δ curve. Although not particularly limited, the content is preferably 1 to 20 parts by mass, more preferably 5 to 15 parts by mass, and even more preferably 7 to 13 parts by mass, relative to 100 parts by mass of the binder resin. The content of the softener contained in the colored resin particles is preferably 1 to 30 parts by mass, more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the binder resin, in order to improve the balance between the storage stability and low-temperature fixability of the toner. The content of the charge control agent contained in the colored resin particles is preferably 0.01 to 15 parts by mass, more preferably 0.03 to 8 parts by mass, based on 100 parts by mass of the binder resin. When the content of the charge control agent is equal to or more than the lower limit, the occurrence of fog can be suppressed, whereas when the content is equal to or less than the upper limit, print smearing can be suppressed.
[0091] The colored resin particles preferably have a volume average particle diameter (Dv) of 3 to 15 μm, more preferably 4 to 12 μm. When Dv is 3 μm or more, the fluidity of the toner can be improved, and the deterioration of transferability and the decrease in image density can be suppressed. When Dv is 15 μm or less, the decrease in image resolution can be suppressed.
[0092] The colored resin particles preferably have a ratio (Dv / Dn) of the volume average particle diameter (Dv) to the number average particle diameter (Dn) of 1.0 to 1.3, more preferably 1.0 to 1.2. By making Dv / Dn 1.3 or less, it is possible to suppress the deterioration of transferability, image density, and resolution. The volume average particle diameter and number average particle diameter of the colored resin particles can be measured, for example, using a particle size analyzer (manufactured by Beckman Coulter, product name: Multisizer) or the like.
[0093] From the viewpoint of image reproducibility, the average circularity of the colored resin particles is preferably from 0.96 to 1.00, more preferably from 0.97 to 1.00, and even more preferably from 0.98 to 1.00. When the average circularity of the colored resin particles is 0.96 or more, the reproducibility of thin lines in printing can be improved. The average circularity of the colored resin particles of the present disclosure is 1 or less, and when a measurement sample is a perfect sphere, the average circularity is 1. In the present disclosure, the circularity is the value obtained by dividing the perimeter of a circle having the same projected area as the particle image by the perimeter of the projected image of the particle. The average circularity is an index showing the degree of unevenness of the surface of the measurement sample, and can be used as a simple method for quantitatively expressing the shape of the particle. The more complex the surface shape of the measurement sample, the smaller the average circularity. The circularity of the colored resin particles can be determined, for example, by taking a projected image of the colored resin particles in a sample liquid using an aqueous solution in which the colored resin particles are dispersed, using a flow particle image analyzer (e.g., FPIA-2100, manufactured by CIMEX, etc.), measuring the perimeter of a circle equal to the projected area of the particle and the perimeter of the projected image of the particle from the projected image, and calculating using Formula 1: (circularity) = (perimeter of a circle equal to the projected area of the particle) / (perimeter of the projected image of the particle). The average circularity is the average value of the circularities of the colored resin particles contained in the sample liquid.
[0094] I-4. First toner of the present disclosure The toner of the first present disclosure can be made from the colored resin particles as they are, but from the viewpoint of adjusting the electrostatic charge, fluidity, storage stability, and the like of the toner, the colored resin particles may be mixed and stirred with an external additive to perform an external addition treatment, thereby adhering the external additive to the surface of the colored resin particles to make a one-component toner. The one-component toner may be mixed and stirred with carrier particles to form a two-component developer.
[0095] The agitator used for the external addition treatment is not particularly limited as long as it is a stirring device capable of adhering an external additive to the surface of colored resin particles. For example, the external addition treatment can be performed using an agitator capable of mixing and stirring, such as FM Mixer (product name, manufactured by Nippon Coke and Engineering Co., Ltd.), Super Mixer (product name, manufactured by Kawada Manufacturing Co., Ltd.), Q Mixer (product name, manufactured by Nippon Coke and Engineering Co., Ltd.), Mechanofusion System (product name, manufactured by Hosokawa Micron Corporation), and Mechano Mill (product name, manufactured by Okada Seiko Co., Ltd.).
[0096] Examples of the external additive include inorganic fine particles such as silica, titanium oxide, aluminum oxide, zinc oxide, tin oxide, calcium carbonate, calcium phosphate, and cerium oxide; organic fine particles such as polymethyl methacrylate resin, silicone resin, and melamine resin; etc. Among these, inorganic fine particles are preferred, and among inorganic fine particles, at least one type of fine particles selected from silica and titanium oxide are preferred, and fine particles made of silica are particularly suitable. Although these external additives can be used alone, it is preferable to use two or more of them in combination.
[0097] In the toner of the first disclosure, the external additive is usually used in a ratio of 0.05 to 6 parts by mass, preferably 0.2 to 5 parts by mass, based on 100 parts by mass of the colored resin particles. When the content of the external additive is 0.05 parts by mass or more, the occurrence of transfer residue can be suppressed, and when the content of the external additive is 6 parts by mass or less, the occurrence of fogging can be suppressed.
[0098] The toner of the first disclosure has a good storage stability and suppresses a decrease in the blocking temperature (heat resistance temperature) by having a temperature-tan δ curve satisfying the formula (I-1) and the formula (I-2). The toner of the first disclosure has a blocking temperature (heat resistance temperature) of preferably 53° C. or higher, more preferably 54° C. or higher, and even more preferably 55° C. or higher. In this disclosure, the blocking temperature of the toner is defined as the maximum temperature at which the mass of the aggregated toner becomes 5% by mass or less of the total amount of the toner when the toner is stored at a certain temperature for 8 hours. The blocking temperature of the toner can be measured by the same method as that for measuring the heat resistance temperature of the toner in the examples described later.
[0099] The toner of the first disclosure has a good low-temperature fixability and suppresses an increase in the fixing temperature due to the temperature-tan δ curve satisfying the formula (I-1) and the formula (I-2). The fixing temperature of the toner of the first disclosure is preferably 180° C. or less, more preferably 170° C. or less, and even more preferably 160° C. or less. In this disclosure, the fixing temperature of the toner is the lowest temperature at which, when a solid image is printed on paper using a printer and a rubbing test is performed on the solid area, a fixing rate of 80% or more is obtained by the following formula as the ratio of the image density after the rubbing test (ID(after)) to the image density before the rubbing test (ID(before)). Retention rate (%) = [ID (later) / ID (earlier)] x 100 The rubbing test is performed by attaching the measurement part to a fastness tester with an adhesive tape, placing a load of 500 g thereon, and rubbing it 5 times back and forth with a rubbing terminal wrapped with a cotton cloth. In the present disclosure, the solid area refers to an area controlled such that a developer adheres to all of the dots (virtually controlling the printer control unit) inside the area.
[0100] II. Toner of the Second Present Disclosure The toner of the second present disclosure is a toner containing colored resin particles including a binder resin, a colorant, a softening agent, and a charge control agent, and an external additive, The glass transition temperature (Tg) specified from the temperature dependence curve of the loss tangent (tanδ) of the toner obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz satisfies 45°C < Tg (°C) < 100°C, In the temperature dependence curve of the loss tangent (tanδ), when the loss tangent (tanδ) at 45°C is tanδ(45°C), the loss tangent (tanδ) at the glass transition temperature (Tg) is tanδ(Tg), the loss tangent (tanδ) at 100°C is tanδ(100°C), and the loss tangent (tanδ) at 130°C is tanδ(130°C), Equation (II-1): 5.00×10 -2 < (tanδ(Tg) - tanδ(45°C)) / (Tg - 45) < 7.60×10 -2 And Equation (II-2): 2.1×10 -3 < (tanδ(130°C) - tanδ(100°C)) / 30 < 4.4×10 -2 It is characterized by satisfying the following.
[0101] Hereinafter, the viscoelastic properties of the toner of the second present disclosure, the method for producing the colored resin particles used in the toner of the second present disclosure and the colored resin particles, the external additive used in the toner of the second present disclosure, and the performance of the toner of the second present disclosure will be described in order.
[0102] II-1. Viscoelastic Properties of the Toner of the Second Present Disclosure The toner of the second disclosure has the following characteristic in the line shape within the range of 45° C. or more and 145° C. or less of the temperature dependency curve of the loss tangent (tan δ) obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz: That is, it has at least one peak within the range of more than 45° C. and less than 100° C., and when the temperature exceeds the temperature at which tan δ of the peak is at its maximum value, tan δ decreases with an increase in temperature, and then tan δ decreases or continues to decrease while increasing and decreasing, and after tan δ reaches its minimum value, tan δ increases gently with a further increase in temperature. In addition, the toner of the second disclosure has a glass transition temperature (Tg) specified from a temperature dependency curve of the loss tangent (tan δ) exceeding 45° C. and less than 100° C., and in the temperature dependency curve of the loss tangent (tan δ), when the loss tangent (tan δ) at 45° C. is tan δ(45° C.), the loss tangent (tan δ) at the glass transition temperature (Tg) is tan δ(Tg), the loss tangent (tan δ) at 100° C. is tan δ(100° C.), and the loss tangent (tan δ) at 130° C. is tan δ(130° C.), Formula (II-1): 5.00×10 -2 <(tanδ(Tg)-tanδ(45℃)) / (Tg-45)<7.60×10 -2 and Formula (II-2): 2.1×10 -3 <(tanδ(130℃)-tanδ(100℃)) / 30<4.4×10 -2 Meet the following. In the formulas (II-1) and (II-2), the values of tan δ are rounded to three decimal places. The value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) in the formula (II-1) is rounded to three significant digits, and the value of (tan δ(130°C)-tan δ(100°C)) / 30 in the formula (II-2) is rounded to two significant digits.
[0103] For the toner of the second disclosure, the dynamic viscoelasticity measurement is performed using the same device and under the same conditions as for the toner of the first disclosure.
[0104] The second toner of the present disclosure has a specific viscoelasticity that satisfies the above formula (II-1) and the above formula (II-2) in a temperature-tan δ curve, and thus has both low-temperature fixability and storage stability improved in a well-balanced manner, and is a toner having excellent performance that was previously difficult to achieve. The smaller the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) shown in the formula (II-1) is within the above-mentioned range, the easier it is to suppress blocking during toner storage, and the storage stability is improved. The smaller the difference between tan δ(Tg) and tan δ(45°C) is, and the higher the Tg is, the smaller the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) is. It is presumed that the viscosity of the toner is not too strong, that is, the movement of polymer chains between toner particles is suppressed, and thus blocking is suppressed, because the difference between tan δ(Tg) and tan δ(45°C) is not too large. In addition, it is presumed that the decrease in elasticity at low temperatures is suppressed, and thus blocking is suppressed. Furthermore, the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) is less than the above-mentioned upper limit in the formula (II-1), the worsening of the storage stability of the toner is suppressed, and further, the occurrence of blowing out after being left at high temperatures is easily suppressed. When the value in formula (II-1) is greater than the lower limit, an increase in the fixing temperature is easily suppressed, and therefore deterioration of low-temperature fixing ability is suppressed. On the other hand, the larger the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (II-2) is within the above numerical range, the lower the fixing temperature tends to be, and the lower temperature fixing property improves. When fixing the toner, the toner gradually deforms with the rise in temperature. When actually fixing the toner, there is a temperature gradient from at least 100°C to 130°C from when the paper to which the toner has been transferred enters the roll until it is discharged. It is presumed that the larger the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (II-2) is, the faster the rise in tan δ after the toner is heated, that is, the faster the increase in the viscosity of the toner, making it possible to fix at a relatively low temperature. Furthermore, by exceeding the lower limit in the formula (II-2), the glossiness of the formed image becomes good. On the other hand, when the formula (II-2) is less than the upper limit, blocking during toner storage is suppressed, and deterioration of storage stability is suppressed. Furthermore, when the formula (II-2) is less than the upper limit, the occurrence of ejection after being left at high temperatures is easily suppressed. The present inventors have also found that the toner having viscoelasticity that satisfies the above formula (II-1) and the above formula (II-2) in the temperature-tan δ curve exhibits the above-mentioned effects, particularly when the toner is subjected to a pressure of 5.0 kgf / cm using a flow tester. 2 The toner softening temperature (T 1 / 2 ) is found to be greater than 124°C and less than 159°C.
[0105] In order to obtain a toner having a viscoelasticity that satisfies the formula (II-1) and the formula (II-2) in the temperature-tan δ curve, for example, the composition, molecular weight, and content of the binder resin contained in the toner, the type and content of the colorant, the glass transition temperature (Tg) and content of the charge control agent, the type and molecular weight of the softener, and the type and content of the external additive, etc., can be appropriately changed to control the viscoelasticity of the toner. Among them, it is effective to adjust the molecular weight and composition of the binder resin, and the type and content of the colorant. The molecular weight and composition, etc. of the binder resin contained in the toner have a large effect on the viscoelasticity of the toner in a low temperature range below the glass transition temperature. Therefore, in order to obtain a viscoelasticity that satisfies the formula (II-1), it is effective to adjust the molecular weight and composition, etc. of the binder resin contained in the toner. On the other hand, the type and content, etc. of the colorant contained in the toner have a large effect on the viscoelasticity of the toner in a temperature range of 100°C to 130°C. Therefore, in order to obtain a viscoelasticity that satisfies the formula (II-2), it is effective to adjust the type and content, etc. of the colorant contained in the toner. More specifically, by adopting a preferred form of each component described later, the temperature-tan δ curve of the toner can be made to satisfy the above formula (II-1) and formula (II-2).
[0106] The toner of the second disclosure satisfies the following formula (II-1) in a temperature-tan δ curve obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. Formula (II-1): 5.00×10 -2 <(tanδ(Tg)-tanδ(45℃)) / (Tg-45)<7.60×10 -2 Among these, the upper limit in the formula (II-1) is preferably 7.40×10 because blocking during storage of the toner is easily suppressed, preservability is easily improved, and the occurrence of ejection after being left at high temperature is easily suppressed. -2 On the other hand, in order to easily suppress an increase in the fixing temperature, the lower limit of the formula (II-1) is preferably less than 5.50×10 -2 It is preferable that the value is equal to or greater than 5.60×10 -2 More preferably, it is 5.90×10 or more.-2 It is more preferably the above, and 6.50×10 -2 It is even more preferably the above.
[0107] The toner of the second disclosure satisfies the following formula (II-2) in the temperature-tanδ curve obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. Formula (II-2): 2.1×10 -3 <(tanδ(130°C) - tanδ(100°C)) / 30 < 4.4×10 -2 Among them, from the viewpoints of improving the low-temperature fixability of the toner and the glossiness of the formed image being likely to be good, the lower limit in the formula (II-2) is preferably more than 3.0×10 -3 It is more preferably more than 3.5×10 -3 It is even more preferably more than 1.20×10 -2 On the other hand, from the viewpoints of being likely to suppress the deterioration of storage stability and being likely to suppress the occurrence of ejection after standing at high temperature, the upper limit in the formula (II-2) is preferably less than 4.1×10 -2 It is more preferably less than 3.8×10 -2 It is even more preferably less than 3.2×10 -2 It is even more preferably the following.
[0108] The toner of the second disclosure satisfies 45°C < Tg(°C) < 100°C for the glass transition temperature (Tg) specified from the temperature-tanδ curve obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz. The glass transition temperature (Tg) is preferably more than 70°C, more preferably more than 73°C, among others, from the viewpoint of suppressing a rapid decrease in elasticity at low temperature and suppressing blocking. On the other hand, from the viewpoint of improving the low-temperature fixability by not allowing the softening start temperature of the toner to become too high, the glass transition temperature (Tg) is preferably 90°C or lower, more preferably 85°C or lower.
[0109] In addition, the toner of the second disclosure has a loss tangent (tan δ) at the glass transition temperature (Tg) of preferably less than 2.410, more preferably less than 2.320, and even more preferably 2.300 or less. By having the tan δ(Tg) be equal to or less than the upper limit, blocking during storage of the toner is easily suppressed, storage stability is easily improved, and the occurrence of spouting after being left at high temperatures is easily suppressed. The lower limit of the tan δ(Tg) is not particularly limited, but from the viewpoint of improving fixability, it is preferably 1.000 or more, and more preferably 1.100 or more.
[0110] The toner of the second disclosure has a loss tangent (tan δ) at 45° C., tan δ(45° C.), of preferably 0.200 or less, more preferably 0.100 or less, and even more preferably 0.050 or less. When the tan δ(45° C.) is equal to or less than the upper limit, blocking during storage of the toner is easily suppressed, storage stability is easily improved, and the occurrence of spouting after being left at high temperatures is easily suppressed. The lower limit of the tan δ (45° C.) is not particularly limited, and it is sufficient if it is 0.000 or more.
[0111] In addition, the toner of the second disclosure has a loss tangent (tan δ) at 100° C., tan δ(100° C.), which is preferably 0.800 or more, more preferably 0.900 or more, and even more preferably 0.950 or more, from the viewpoint that the low-temperature fixing property of the toner is easily improved, while it is preferably 1.500 or less, more preferably 1.400 or less, from the viewpoint that the deterioration of the storage stability of the toner is easily suppressed and the occurrence of spraying after being left at high temperatures is easily suppressed.
[0112] In addition, the toner of the second disclosure has a loss tangent (tan δ) at 130° C., tan δ(130° C.), which is preferably 1.000 or more in terms of easily improving the low-temperature fixing property of the toner, and on the other hand, is preferably 3.000 or less, more preferably 2.500 or less, and even more preferably 2.300 or less in terms of easily preventing deterioration of the storage stability of the toner and easily preventing the occurrence of ejection after being left at high temperatures.
[0113] The toner of the second disclosure is subjected to a flow test at a pressure of 5.0 kgf / cm 2 The softening temperature (T 1 / 2 The softening temperature (T 1 / 2 When the toner has a viscoelasticity that satisfies the formula (II-1) and the formula (II-2) in the temperature-tan δ curve, the toner can improve low-temperature fixability and storage stability in a well-balanced manner, and can easily suppress the occurrence of ejection after being left at high temperature. 1 / 2 When the content of the toner particles is within the above range, the fixing temperature of the toner is lowered, making the toner easy to handle, and generation of volatile organic compounds (VOCs: Volatile Organic Compounds) such as styrene and siloxane substances and ultra fine particles (UFPs) due to heating during toner fixing is easily suppressed. The softening temperature (T 1 / 2 From the viewpoint of improving storage stability, the softening temperature (T 1 / 2 ) is preferably less than 165°C, more preferably 163°C or less, and even more preferably less than 159°C. The softening temperature (T 1 / 2 The softening temperature (T 1 / 2 The softening temperature (T 1 / 2 ) tends to decrease. In addition, the larger the weight average molecular weight of the polymer contained in the binder resin, the lower the softening temperature (T 1 / 2 ) tends to rise.
[0114] The flow tester was used at a pressure of 5.0 kgf / cm 2 The softening temperature (T 1 / 2 The softening temperature (T) can be determined from a flow curve (piston stroke-temperature) measured under the following measurement conditions using a Shimadzu flow tester (product name: CFT-500C). Specifically, in the flow curve, half the difference between the piston stroke at the end of outflow and the minimum value of the piston stroke is calculated, and the temperature at the position where the calculated value and the minimum value are added is defined as the softening temperature (T 1 / 2 ) can be obtained. (Measurement conditions) Starting temperature: 35℃ Heating rate: 3℃ / min Preheat time: 5 minutes Cylinder pressure: 5.0kgf / cm 2 (5kg method) Die hole diameter: 0.5mm Die length: 1.0mm Sample input amount: 1.0~1.3g
[0115] II-2. Thermal properties of toner In addition, toner with improved low-temperature fixing properties tends to be easily sprayed out from the developing roller after being left at high temperatures, so there has been a demand for a toner that has excellent low-temperature fixing properties, good storage stability, and can suppress the occurrence of spraying out after being left at high temperatures. The toner of the second disclosure is further susceptible to jetting out after being left at high temperatures. In particular, in the toner of the second disclosure, when the toner has an apparent glass transition temperature (Tg2) of 68°C to 74°C when heated at a temperature increase rate of 1000 K / sec and an apparent heat generation initiation temperature of 50°C to 62°C when cooled at a temperature decrease rate of 1000 K / sec, as measured by differential scanning calorimetry using a high-speed differential scanning calorimeter, both low-temperature fixability and storage stability are improved in a well-balanced manner, and jetting out after being left at high temperatures is suppressed.
[0116] In the second toner of the present disclosure, it is preferable that the toner has an apparent glass transition temperature (Tg2) of 68°C to 74°C when heated at a heating rate of 1000 K / sec, and a heat generation starting temperature of 50°C to 62°C when cooled at a cooling rate of 1000 K / sec, as measured by differential scanning calorimetry using a high-speed differential scanning calorimeter.
[0117] In the present disclosure, the differential scanning calorimetry (DSC) using the high-speed differential scanning calorimeter can be performed using an ultrahigh-speed DSC device (Flash DSC, manufactured by Mettler Toledo) under the following temperature conditions (1) to (5). (1) Hold at 0°C for 0.1 seconds (2) Heat from 0°C to 150°C at 1000K / sec. (3) Hold at 150°C for 60 seconds. (4) The temperature is decreased from 150°C to 0°C at -1000K / sec. (5) Hold at 0°C for 1 second.
[0118] FIG. 3 shows how to determine the apparent glass transition temperature (Tg2) of a toner when heated at a heating rate of 1000 K / sec in high speed differential scanning calorimetry, and the heat generation initiation temperature of a toner when cooled at a heating rate of 1000 K / sec. The apparent glass transition temperature (Tg2) is the temperature at the intersection of a straight line extending from the low-temperature baseline to the high-temperature side of the DSC curve during heating and a tangent drawn at the step-like change in the glass transition or at the point where the slope of the endothermic peak due to enthalpy relaxation is maximum. The heat generation onset temperature is defined as the temperature at which heat generation begins when the DSC curve during cooling moves away from the baseline and an exothermic peak appears.
[0119] The present inventors have discovered that by using the apparent glass transition temperature and heat generation onset temperature measured at a high heating and cooling rate of 1000 K / sec, which is equivalent to that during fixing, it is possible to indirectly evaluate the behavior of the components of the toner composition in a state where they coexist and interact with each other in a phenomenon of rapid heating and cooling, such as fixing property, and to control the low-temperature fixing property of the toner. In normal DSC measurements, with a slow heating rate of 10 K / s, semi-crystalline samples containing amorphous components may reorganize and recrystallize during heating, which may appear as a peak, and if the peak caused by the above overlaps with the glass transition temperature, it becomes difficult to determine the exact temperature. In contrast, with a high heating rate of 1000 K / s, there is no time for recrystallization, etc., so it is thought that the behavior during heating during fixing can be reproduced as is. With a high heating rate of 1000 K / s, simple endothermic behavior is observed, so multiple peaks tend to merge into one, and the phase transition during fixing appears simplified. In addition, in the case of a normal DSC measurement, when the temperature is decreased at a low rate such as 10 K / sec, the amorphous component such as the resin and the crystalline component such as the softener slowly phase separate from the compatible state, so the temperature at which the crystallization of the crystalline component begins is thought to be less affected by the amorphous component. In contrast, in the case of a high rate of temperature decrease such as 1000 K / sec, the amorphous component such as the resin and the crystalline component such as the softener are rapidly cooled from the compatible state, so it is thought that the crystallization of the crystalline component occurs shortly before phase separation, that is, while they interfere with each other. It was found that the order of the toners with high and low heat generation start temperatures measured at a high rate of temperature decrease of 1000 K / sec, which is equivalent to that during fixing, may differ from the order of the toners with high and low heat generation start temperatures measured at a low rate of temperature decrease such as 10 K / sec. It is thought that the heat generation start temperature measured at a high rate of temperature decrease of 1000 K / sec, which is equivalent to that during fixing, can evaluate the temperature at which crystallization begins when the crystalline component in the toner during fixing is affected by the surrounding amorphous components.
[0120] The toner of the second disclosure, in which the toner has an apparent glass transition temperature (Tg2) of 68°C to 74°C when heated at a heating rate of 1000 K / sec and a heat generation initiation temperature of 50°C to 62°C when cooled at a cooling rate of 1000 K / sec, has excellent low-temperature fixing properties and good storage stability, and can suppress the occurrence of spraying after being left at high temperatures. A low heat generation initiation temperature within the above-mentioned specific range means that in the fixing process, when the toner is heated to melt and then rapidly cooled, the fluidity of the molten binder resin is maintained and at the same time, the crystallization of the softener is slow, so that the toner spreads over the paper surface and is likely to improve fixability. By setting the apparent glass transition temperature (Tg2) and the heat generation onset temperature to the upper limit or lower, the low temperature fixability is improved. By setting the apparent glass transition temperature (Tg2) and the heat generation onset temperature to the lower limit or higher, the deterioration of the storage stability is suppressed, and the occurrence of eruptions after being left at high temperature can be suppressed.
[0121] In order to obtain a toner having thermal properties that satisfy the specific ranges of apparent glass transition temperature (Tg2) and heat generation start temperature, the thermal properties of the toner can be controlled by appropriately changing, for example, the composition, molecular weight, and content of the binder resin contained in the toner, the type and content of the colorant, the glass transition temperature (Tg) and content of the charge control agent, the type and molecular weight of the softener, and the type and content of the external additive. Among these, it is effective to adjust the molecular weight and composition of the binder resin, and the type and content of the colorant. More specifically, the specific ranges of apparent glass transition temperature (Tg2) and heat generation start temperature can be satisfied by adopting the preferred form of each component described later.
[0122] In particular, the upper limit of the apparent glass transition temperature (Tg2) is preferably 73° C. or less, and more preferably 72° C. or less, in view of the ease with which an increase in the fixing temperature can be suppressed. In addition, from the viewpoints of easily suppressing blocking during storage of the toner, easily improving storage stability, and easily suppressing the occurrence of ejection after being left at high temperatures, the lower limit of the heat generation initiation temperature is preferably 52° C. or more, and more preferably 54° C. or more. On the other hand, from the viewpoint of easily suppressing an increase in the fixing temperature, the upper limit of the heat generation initiation temperature is preferably 60° C. or less, and more preferably 58° C. or less.
[0123] II-3. Method for producing colored resin particles The colored resin particles used in the toner of the second disclosure can be produced by employing a wet method or a dry method, like the colored resin particles used in the toner of the first disclosure, but a wet method is preferred, and among the wet methods, a suspension polymerization method is particularly preferred, and the colored resin particles can be produced by the following process.
[0124] (A) Suspension polymerization method (A-1) Preparation of polymerizable monomer composition First, a polymerizable monomer, a colorant, a softener, a charge control agent, and, if necessary, other additives such as a molecular weight regulator and a styrene-based thermoplastic elastomer are mixed to prepare a polymerizable monomer composition. The mixing for preparing the polymerizable monomer composition is performed, for example, using a media-type dispersing machine. In the following, the colored resin particles used in the toner of the first disclosure may be referred to as the colored resin particles of the first disclosure, and the colored resin particles used in the toner of the second disclosure may be referred to as the colored resin particles of the second disclosure.
[0125] The polymerizable monomer used in the production of the colored resin particles of the second disclosure may be, for example, the same as the polymerizable monomer used in the production of the colored resin particles of the first disclosure. The polymerizable monomer used in the production of the colored resin particles of the second disclosure preferably contains a monovinyl monomer as a main component, and may further contain a macromonomer or a crosslinkable polymerizable monomer. The point where the temperature-tan δ curve of the toner easily satisfies the formula (II-1) and the formula (II-2), 1 / 2) is likely to be in the preferred range, and the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to be in the specific range, the polymerizable monomer preferably contains at least one monovinyl monomer selected from the group consisting of styrene, a styrene derivative, an acrylic acid ester, and a methacrylic acid ester, more preferably contains at least one monovinyl monomer selected from the group consisting of styrene, an acrylic acid ester, and a methacrylic acid ester, and even more preferably contains styrene and at least one selected from the group consisting of an acrylic acid ester and a methacrylic acid ester. In addition, the temperature-tan δ curve of the toner is likely to satisfy the formula (II-1) and the formula (II-2), and the softening temperature (T 1 / 2 ) is likely to be in the preferred range, and the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to be in the specific ranges. Therefore, among these, the acrylic ester is preferably at least one selected from the group consisting of n-butyl acrylate, propyl acrylate, and 2-ethylhexyl acrylate, and among these, the methacrylic ester is preferably at least one selected from the group consisting of n-butyl methacrylate, propyl methacrylate, and 2-ethylhexyl methacrylate.
[0126] The content of styrene in 100 parts by mass of the total of the monovinyl monomers is preferably 60 parts by mass or more, more preferably 70 parts by mass or more, even more preferably 80 parts by mass or more, and even more preferably 90 parts by mass or more. The higher the content of styrene, the higher the apparent glass transition temperature (Tg2) of the toner becomes, and the lower the softening temperature (T 1 / 2 ) becomes higher, and the glass transition temperature (Tg) of the toner tends to become higher.
[0127] In addition, the temperature-tan δ curve of the toner is likely to satisfy the formula (II-1) and the formula (II-2), and the softening temperature (T 1 / 2) is likely to be in the preferred range, and the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to be in the specific range, the monovinyl monomer contains styrene and at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters, and the mass ratio of styrene to the total of the acrylic acid esters and methacrylic acid esters (styrene:(meth)acrylic acid ester) is preferably in the range of 50:50 to 90:10, more preferably in the range of 60:40 to 80:20, and particularly preferably in the range of 70:30 to 80:20.
[0128] When the polymerizable monomer contains a polymerizable monomer other than the monovinyl monomer, the content of the monovinyl monomer is appropriately adjusted so that the temperature-tan δ curve of the toner satisfies the formula (II-1) and the formula (II-2), and preferably further so that the apparent glass transition temperature (Tg2) and the heat generation start temperature of the toner are in the specific range. Although not particularly limited, the total amount of the monovinyl monomer is preferably 90 parts by mass or more, more preferably 95 parts by mass or more, relative to 100 parts by mass of the total amount of the polymerizable monomer. The monovinyl monomer may be used alone or in combination of two or more kinds.
[0129] As the macromonomer, at least one selected from polyacrylic acid ester macromonomers and polymethacrylic acid ester macromonomers can be preferably used from the viewpoint of easy control of the apparent glass transition temperature (Tg2) of the toner and the glass transition temperature (Tg) in the temperature-tan δ curve. Examples of the acrylic acid ester used in the polyacrylic acid ester macromonomer include the same acrylic acid ester usable as the monovinyl monomer, and examples of the methacrylic acid ester used in the polymethacrylic acid ester macromonomer include the same methacrylic acid ester usable as the monovinyl monomer. Among them, it is preferable to appropriately select and use a macromonomer that, when contained in the polymerizable monomer, makes the glass transition temperature (Tg) of the resulting binder resin higher than when not contained, because it is easy to bring the apparent glass transition temperature (Tg2) of the toner and the glass transition temperature (Tg) in the temperature-tan δ curve into the preferred range. When the polymerizable monomer contains the macromonomer, the content of the macromonomer is appropriately adjusted so that the temperature-tan δ curve of the toner satisfies the formula (II-1) and the formula (II-2), and is not particularly limited, but is preferably used in a ratio of 0.03 to 5 parts by mass, more preferably 0.05 to 1 part by mass, relative to 100 parts by mass of the monovinyl monomer. The macromonomer may be used alone or in combination of two or more kinds.
[0130] When the polymerizable monomer contains the crosslinkable polymerizable monomer, the softening temperature (T 1 / 2) is likely to be in the preferred range, the apparent glass transition temperature (Tg2) and heat generation onset temperature are likely to be in the specific range, and gloss is likely to be improved, the content of the crosslinkable polymerizable monomer is preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, and even more preferably 0.05 parts by mass or less, relative to 100 parts by mass of the monovinyl monomer, and it is most preferable that no crosslinkable polymerizable monomer is contained. The crosslinkable polymerizable monomer may be used alone or in combination of two or more kinds.
[0131] The content of the polymerizable monomers is appropriately adjusted so that the temperature-tan δ curve of the toner satisfies the formula (II-1) and the formula (II-2), and preferably so that the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are in the specific ranges. Although not particularly limited, the total content of the polymerizable monomers is preferably 60 to 95 parts by mass, more preferably 65 to 90 parts by mass, and even more preferably 70 to 85 parts by mass, per 100 parts by mass of the total solid content contained in the polymerizable monomer composition.
[0132] The colorant contained in the toner of the second disclosure can be appropriately selected from colorants used in conventional toners and is not particularly limited. When preparing a color toner, black, cyan, yellow, and magenta colorants can be used. Examples of the black colorant, cyan colorant, yellow colorant, and magenta colorant include the same colorants as those usable in the toner of the first disclosure. The colorant contained in the toner of the second disclosure is a colorant having a temperature-tan δ curve that is likely to satisfy the above formula (II-1) and the above formula (II-2), and has a softening temperature (T 1 / 2Since the apparent glass transition temperature (Tg2) and the heat generation starting temperature of the toner are likely to be in the preferred range, the low-temperature fixability and storage stability of the toner are likely to be improved, and since the apparent glass transition temperature (Tg2) and the heat generation starting temperature of the toner are in the specific range, the hot offset property is likely to be maintained. Therefore, preferably, a cyan colorant containing a cyan pigment, a yellow colorant containing a combination of a yellow dye and a yellow pigment, or a magenta colorant containing a magenta pigment is used, more preferably, a cyan colorant containing a phthalocyanine cyan pigment, a yellow colorant containing a combination of a yellow dye and a yellow pigment containing a chlorine atom, or a magenta colorant containing a quinacridone magenta pigment is used, and even more preferably, a cyan colorant containing at least one selected from CI Pigment Blue 15:3 and CI Pigment Blue 15:4, a yellow colorant containing a combination of CI Solvent Yellow 98 and CI Pigment Yellow 214, or a magenta colorant containing at least one selected from CI Pigment Red 122 and CI Pigment Violet 19 is used.
[0133] As a quinacridone magenta pigment preferably used as a magenta colorant, a mixed crystal of CI Pigment Violet 19 and CI Pigment Red 122 can be preferably used because of its excellent weather resistance and image density. The mixed crystal of CI Pigment Violet 19 and CI Pigment Red 122 can be produced, for example, by the method described in U.S. Pat. No. 3,160,510 in which the mixed crystal components are simultaneously recrystallized from sulfuric acid or other suitable solvent, and if necessary, salt-ground and then treated with a solvent, or by the method described in German Patent Application Publication No. 1,217,333 in which a mixture of substituted diaminoterephthalic acids is cyclized and then treated with a solvent. In the mixed crystal of CI Pigment Violet 19 and CI Pigment Red 122, the mass ratio of CI Pigment Violet 19 to CI Pigment Red 122 is usually 80:20 to 20:80, preferably 70:30 to 30:70, and more preferably 60:40 to 40:60.
[0134] The content of the colorant is usually 1 to 20 parts by mass, preferably 5 to 15 parts by mass, and more preferably 7 to 13 parts by mass, based on 100 parts by mass of the total amount of the polymerizable monomer. When the content of the colorant is within the above range, the temperature-tan δ curve of the toner easily satisfies the above formula (II-1) and the above formula (II-2), and the softening temperature (T 1 / 2 ) is likely to be in the preferred range, and further, the apparent glass transition temperature (Tg2) and the heat generation starting temperature of the toner are likely to be in the specific range. The colorants can be used alone or in combination of two or more.
[0135] The polymerizable monomer composition contains a softener. By containing the softener, the releasability of the toner from the fixing roll during fixing can be improved. The softener can be any softener that is generally used as a toner softener or release agent, and can be the same as the softener that can be used for the colored resin particles of the first present disclosure.
[0136] The weight average molecular weight Mw of the softener is not particularly limited, but is preferably within a range of 400 to 3500, and more preferably 500 to 3000. The larger the weight average molecular weight Mw of the softener, the higher the softening temperature (T 1 / 2 ) tends to be high, and the apparent glass transition temperature (Tg2) and the heat generation initiation temperature of the toner tend to be high.
[0137] In order to adjust the viscoelasticity of the toner and adjust the apparent glass transition temperature (Tg2) and the heat generation initiation temperature to improve the balance between the storage stability and low-temperature fixability of the toner, the melting point of the softener is preferably within a range of 50 to 90°C, more preferably within a range of 60 to 85°C, and even more preferably within a range of 70 to 80°C. The content of the softener is not particularly limited, but from the viewpoint of adjusting the viscoelasticity of the toner and adjusting the apparent glass transition temperature (Tg2) and the heat generation initiation temperature to improve the balance between the storage stability and low-temperature fixability of the toner, the softener is preferably used in a ratio of 1 to 30 parts by mass, more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the monovinyl monomer. The softening agents may be used alone or in combination of two or more.
[0138] The polymerizable monomer composition contains a positively or negatively chargeable charge control agent, which can improve the chargeability of the toner. The charge control agent is not particularly limited as long as it is one that is generally used as a charge control agent for toners. Among the charge control agents, a positively or negatively charged charge control resin is preferred because it has high compatibility with polymerizable monomers and can impart stable chargeability (charge stability) to toner particles. Furthermore, from the viewpoint of obtaining a positively charged toner, a positively charged charge control resin is more preferably used.
[0139] Examples of the positively or negatively charged charge control resin include the same functional group-containing copolymers that can be used for the colored resin particles of the first present disclosure. The functional group-containing copolymer used as the positively or negatively charged charge control resin is preferably one having a ratio of functional group-containing structural units of 3% by mass or less, more preferably 2.5% by mass or less, in order to easily satisfy the formula (II-1) and the formula (II-2) in the temperature-tan δ curve of the toner, and to easily make the apparent glass transition temperature (Tg2) and the heat generation start temperature of the toner fall within the specific range. On the other hand, the ratio of functional group-containing structural units in the functional group-containing copolymer is preferably 0.5% by mass or more, in order to easily improve the charge stability and storage stability of the toner and easily suppress the occurrence of blowing out after being left at high temperatures. It is presumed that the charge control resin contains a sufficient amount of functional groups, which makes it easy for the charge control resin to localize near the surface of the colored resin particles, and the charge control resin functions like a shell of the colored resin particles, thereby improving the storage stability of the toner and suppressing the occurrence of blowing out after being left at high temperatures.
[0140] The functional group-containing copolymer used as the positively or negatively charged charge control resin is preferably a styrene-acrylic resin, because it has high compatibility with the polymerizable monomer, the toner temperature-tan δ curve is likely to satisfy the formula (II-1) and the formula (II-2), and the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to fall within the specific ranges.
[0141] The functional group-containing copolymer used as a positively or negatively charged charge control resin preferably has a glass transition temperature (Tg) of 50 to 110° C., more preferably 60 to 100° C. When the glass transition temperature (Tg) of the functional group-containing copolymer is within the above range, the toner temperature-tan δ curve is likely to satisfy the formula (II-1) and the formula (II-2), the apparent glass transition temperature (Tg2) and the heat generation start temperature of the toner are likely to be within the specific range, and the storage stability of the toner can be improved. The functional group-containing copolymer is likely to be localized near the surface of the colored resin particles and can function like a shell, so it is presumed that when the Tg of the functional group-containing copolymer is within the above range, the storage stability of the toner is improved due to the sufficiently high Tg.
[0142] The functional group-containing copolymer used as the positively or negatively charged charge control resin preferably has a weight average molecular weight Mw of 5,000 to 30,000, and more preferably 10,000 to 25,000.
[0143] Examples of the positively or negatively chargeable charge control agent other than the charge control resin include the same ones as those usable for the colored resin particles of the first present disclosure.
[0144] In the present disclosure, the charge control agent is usually used in a proportion of 0.01 to 10 parts by mass, preferably 0.03 to 8 parts by mass, relative to 100 parts by mass of the monovinyl monomer. When the content of the charge control agent is 0.01 parts by mass or more, the occurrence of fog can be suppressed, whereas when the amount of the charge control agent added is 10 parts by mass or less, print smearing can be suppressed. The charge control agent can be used alone or in combination of two or more kinds.
[0145] The polymerizable monomer composition preferably further contains a molecular weight modifier. The molecular weight modifier is not particularly limited as long as it is a molecular weight modifier that is generally used for toners, and examples thereof include the same molecular weight modifiers as those that can be used in the production of the colored resin particles of the first present disclosure.
[0146] In the toner of the second disclosure, the temperature-tan δ curve of the toner is likely to satisfy the formula (II-1) and the formula (II-2), and the softening temperature (T 1 / 2 Since the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to be in the above-mentioned preferred range, and the apparent glass transition temperature (Tg3) and the heat generation onset temperature of the toner are likely to be in the above-mentioned specific range, it is preferable to adjust the content of the molecular weight regulator so that the weight average molecular weight Mw of the polymer contained in the binder resin is in the preferred range described below. The molecular weight regulator is used in a ratio of preferably 1.0 to 3.0 parts by mass, more preferably 1.1 to 2.0 parts by mass, per 100 parts by mass of the monovinyl monomer. The molecular weight regulators may be used alone or in combination of two or more kinds. The higher the content of the molecular weight regulator, the lower the weight average molecular weight of the polymer contained in the binder resin tends to be, and the lower the softening temperature (T 1 / 2 ) tends to be lower, and the apparent glass transition temperature (Tg2) and the heat generation starting temperature of the toner tend to be lower. In addition, the greater the content of the molecular weight modifier, the greater the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) shown in the formula (II-1) and the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (II-2) in the temperature-tan δ curve of the toner tend to be. In addition, the greater the content of the molecular weight modifier, the lower the glass transition temperature (Tg) of the toner tends to be, and the tan at Tg, tan δ at 100°C, and tan δ at 130°C tend to be increased.
[0147] The polymerizable monomer composition may further contain a styrene-based thermoplastic elastomer. By containing a styrene-based thermoplastic elastomer, the softening temperature (T 1 / 2Here, the styrene-based thermoplastic elastomer refers to a random, block, graft, or other copolymer of a styrene-based monomer and at least one other monomer selected from monoolefins, diolefins, and the like that can be copolymerized with the styrene-based monomer, and a hydrogenated product of such a copolymer. Furthermore, by containing a styrene-based thermoplastic elastomer in the toner, the fixability of the toner can be improved while maintaining the heat resistance temperature of the toner.
[0148] Representative examples of styrene-based thermoplastic elastomers include styrene-butadiene-styrene type block copolymers, styrene-butadiene type block copolymers, styrene-isoprene-styrene type block copolymers, styrene-isoprene type block copolymers, styrene-butadiene-isoprene-styrene type block copolymers, and hydrogenated products thereof; styrene-ethylene-butylene-styrene type block copolymers, styrene-ethylene-propylene-styrene type block copolymers, and styrene-ethylene-ethylene-propylene-styrene type block copolymers. Among these styrene-based thermoplastic elastomers, from the viewpoint of optimizing the balance between the storage stability and low-temperature fixability of the toner, a styrene-isoprene-styrene type block copolymer can be suitably used.
[0149] The styrene content in the styrene-based thermoplastic elastomer is preferably 15 to 70% by mass, more preferably 15 to 60% by mass, and even more preferably 20 to 40% by mass. When the styrene content is equal to or more than the lower limit, the proportion of hydrocarbon units is not too high, and the fixed toner is less likely to peel off from the fixing surface, so that a decrease in fixability is suppressed. On the other hand, when the styrene content is equal to or less than the upper limit, the compatibility with the binder resin is not too high, and a decrease in the storage stability of the toner is suppressed.
[0150] The weight average molecular weight Mw of the styrene-based thermoplastic elastomer is not particularly limited, but is preferably 50,000 to 350,000, and more preferably 80,000 to 250,000, from the viewpoint of excellent effect of improving the fixability of the toner while maintaining the heat resistance temperature of the toner.
[0151] The content of the styrene-based thermoplastic elastomer is set to be equal to or lower than the softening temperature (T 1 / 2 ) is within the above-mentioned preferred range, and the apparent glass transition temperature (Tg2) and the heat generation initiation temperature of the toner are within the above-mentioned preferred range. Although not particularly limited, the amount of the toner is preferably adjusted to 0.5 to 10 parts by mass, more preferably 1 to 8 parts by mass, and further preferably 2 to 6 parts by mass, relative to 100 parts by mass of the monovinyl monomer. The styrene-based thermoplastic elastomers may be used alone or in combination of two or more.
[0152] (A-2) Suspension step for obtaining a suspension (droplet formation step) The droplet forming step carried out in the production of colored resin particles according to the second present disclosure may be similar to the droplet forming step carried out in the production of colored resin particles according to the first present disclosure.
[0153] (A-3) Polymerization process The polymerization step performed in the production of the colored resin particles of the second disclosure may be the same as the polymerization step performed in the production of the colored resin particles of the first disclosure, and it is preferable to use core-shell type colored resin particles as in the production of the colored resin particles of the first disclosure. By covering a core layer made of a material having a low softening point with a material having a higher softening point, it is easy to satisfy the formula (II-1) and the formula (II-2) in the temperature-tan δ curve, and the low temperature fixability and storage stability of the toner can be improved in a well-balanced manner.
[0154] (A-4) Washing, filtering, dehydrating, and drying steps The washing, filtering, dehydrating, and drying steps carried out in the production of the colored resin particles of the second disclosure may be similar to the washing, filtering, dehydrating, and drying steps carried out in the production of the colored resin particles of the first disclosure.
[0155] (B) Crushing method When the colored resin particles are produced by a pulverization method, for example, any pulverization method that can be used for producing the colored resin particles of the first present disclosure can be used.
[0156] II-4. Colored resin particles The colored resin particles can be obtained by the above-mentioned production method such as (A) the suspension polymerization method or (B) the pulverization method. The colored resin particles contained in the toner of the second aspect of the present disclosure will be described below. The colored resin particles described below include both core-shell type and non-core-shell type particles.
[0157] The colored resin particles used in the toner of the second present disclosure contain a binder resin, a colorant, a softener, and a charge control agent, and may further contain other additives such as a styrene-based thermoplastic elastomer, if necessary.
[0158] The binder resin contained in the colored resin particles may be, for example, a polymer obtained by polymerizing the polymerizable monomers listed in the above-mentioned (A) suspension polymerization method. The polymer of the polymerizable monomer contained as the binder resin may form a cross-linked bond with the styrene-based thermoplastic elastomer in the colored resin particles. The preferred polymerizable monomers from which each structural unit of the polymer is derived are the same as the preferred polymerizable monomers described in the above-mentioned (A) suspension polymerization method. The toner is likely to satisfy the formulas (II-1) and (II-2) in the temperature-tan δ curve, and the softening temperature (T 1 / 2) is likely to be in the preferred range, the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to be in the specific range, and the low-temperature fixability and storage stability of the toner are likely to be improved in a well-balanced manner. Therefore, the binder resin contained in the colored resin particles preferably contains a polymer of one or more polymerizable monomers including at least one monovinyl monomer selected from the group consisting of styrene, acrylic acid esters, and methacrylic acid esters, and more preferably contains a polymer of one or more polymerizable monomers including styrene and at least one selected from the group consisting of acrylic acid esters and methacrylic acid esters.
[0159] The weight average molecular weight Mw of the polymer contained in the binder resin is such that the toner easily satisfies the above formula (II-1) and the above formula (II-2) in the temperature-tan δ curve, and the softening temperature (T 1 / 2 ) is likely to fall within the preferred range, the apparent glass transition temperature (Tg2) and the heat generation starting temperature are likely to fall within the specific ranges, and the low-temperature fixability and storage stability of the toner are likely to be improved in a well-balanced manner. 4 Above 2.00 x 10 5 Among these, the lower limit of the weight average molecular weight Mw is more preferably 2.00×10 or less from the viewpoint of improving the storage stability of the toner. 4 More preferably, 3.00×10 4 On the other hand, the upper limit of the weight average molecular weight Mw is more preferably 1.50×10 5 More preferably, 1.00×10 5 The polymer contained in the binder resin is typically a polymer of the above-mentioned polymerizable monomer. As the weight average molecular weight Mw of the polymer decreases, the toner Tg decreases and tan δ(Tg) increases, so the value of (tan δ(Tg)-tan δ(45°C)) / (Tg-45) shown in the formula (II-1) tends to increase. In addition, as the weight average molecular weight Mw of the polymer decreases, both tan δ(100°C) and tan δ(130°C) of the toner tend to increase, but since the increase in tan δ(130°C) is more likely to be greater, the value of (tan δ(130°C)-tan δ(100°C)) / 30 shown in the formula (II-2) tends to increase. In addition, as the weight average molecular weight Mw of the polymer increases, the softening temperature (T 1 / 2 ) tends to be high, and the apparent glass transition temperature (Tg2) and the heat generation starting temperature of the toner tend to be high. In addition, by making the weight average molecular weight Mw of the polymer equal to or less than the upper limit, deterioration of storage stability is easily suppressed. The weight average molecular weight Mw of the polymer contained in the binder resin can be determined by the same method as that described for the colored resin particles of the first disclosure. In the colored resin particles of the second disclosure, examples of the polymer other than the polymer contained as the binder resin include a charge control resin, a softener, and a styrene-based thermoplastic elastomer.
[0160] The binder resin contained in the colored resin particles is typically a polymer of the polymerizable monomer, but may contain a small amount of polyester resin, epoxy resin, or the like that has been widely used as a binder resin for toners, or unreacted polymerizable monomer, as long as the toner satisfies the formula (II-1) and the formula (II-2) in the temperature-tan δ curve. Among them, the content of the polyester resin contained in 100 parts by mass of the binder resin is preferably 5 parts by mass or less, more preferably 1 part by mass or less, and even more preferably 0.1 parts by mass or less, and it is particularly preferable that the binder resin does not contain a polyester resin. By having the content of the polyester resin be equal to or less than the upper limit, the environmental stability of the toner can be improved, and in particular, the change in the charge of the toner due to the change in humidity can be suppressed. Furthermore, when the binder resin contains a resin other than the polymer of the polymerizable monomer, the content of the polymer of the polymerizable monomer in 100 parts by mass of the binder resin is preferably 95 parts by mass or more, more preferably 97 parts by mass or more, and even more preferably 99 parts by mass or more, from the viewpoints that the temperature-tan δ curve of the toner is likely to satisfy the formula (II-1) and the formula (II-2), and the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to be in the specific ranges.
[0161] The total content of the binder resin is preferably 60 to 95 parts by mass, more preferably 65 to 90 parts by mass, and even more preferably 70 to 85 parts by mass, relative to 100 parts by mass of the total solid content contained in the colored resin particles, because the toner is likely to satisfy the formula (II-1) and the formula (II-2) in the temperature-tan δ curve, and the apparent glass transition temperature (Tg2) and the heat generation onset temperature of the toner are likely to be in the specific ranges.
[0162] The colorant, softener, charge control agent and styrene-based thermoplastic elastomer contained in the colored resin particles are the same as those mentioned in the above suspension polymerization method (A). The content of the colorant contained in the colored resin particles is appropriately adjusted according to the type of colorant so that a desired color is obtained and the toner satisfies the formula (II-1) and the formula (II-2) in the temperature-tan δ curve, preferably so that the apparent glass transition temperature (Tg2) and the heat generation starting temperature of the toner are in the specific ranges. Although not particularly limited, the content is preferably 1 to 20 parts by mass, more preferably 5 to 15 parts by mass, and even more preferably 7 to 13 parts by mass, relative to 100 parts by mass of the binder resin. The content of the softener contained in the colored resin particles is preferably 1 to 30 parts by mass, more preferably 5 to 20 parts by mass, relative to 100 parts by mass of the binder resin, in order to improve the balance between the storage stability and low-temperature fixability of the toner. The content of the charge control agent contained in the colored resin particles is preferably 0.01 to 15 parts by mass, more preferably 0.03 to 8 parts by mass, based on 100 parts by mass of the binder resin. When the content of the charge control agent is equal to or more than the lower limit, the occurrence of fog can be suppressed, whereas when the content is equal to or less than the upper limit, print smearing can be suppressed. The content of the styrene-based thermoplastic elastomer contained in the colored resin particles is appropriately adjusted so that the toner satisfies the formula (II-1) and the formula (II-2) in the temperature-tan δ curve, and preferably further so that the apparent glass transition temperature (Tg2) and the heat generation starting temperature of the toner are within the specific ranges. Although not particularly limited, the content is preferably 0.5 to 10 parts by mass, more preferably 1 to 8 parts by mass, and even more preferably 2 to 6 parts by mass, relative to 100 parts by mass of the binder resin.
[0163] The colored resin particles preferably have a volume average particle diameter (Dv) of 3 to 15 μm, more preferably 4 to 12 μm. When Dv is 3 μm or more, the fluidity of the toner can be improved, and the deterioration of transferability and the decrease in image density can be suppressed. When Dv is 15 μm or less, the decrease in image resolution can be suppressed.
[0164] The colored resin particles preferably have a ratio (Dv / Dn) of their volume average particle diameter (Dv) to number average particle diameter (Dn) of 1.0 to 1.3, more preferably 1.0 to 1.2. By making Dv / Dn 1.3 or less, deterioration in transferability, image density, and resolution can be suppressed.
[0165] From the viewpoint of image reproducibility, the average circularity of the colored resin particles is preferably from 0.96 to 1.00, more preferably from 0.97 to 1.00, and even more preferably from 0.98 to 1.00. When the colored resin particles have an average circularity of 0.96 or more, the reproducibility of thin lines in printing can be improved.
[0166] II-5. Second Toner of the Present Disclosure The toner of the second present disclosure can be made into a toner using the colored resin particles as they are, but from the viewpoint of adjusting the electrostatic charge, fluidity, storage stability, and the like of the toner, the colored resin particles may be mixed and stirred with an external additive to perform an external addition treatment, thereby adhering the external additive to the surface of the colored resin particles to make a one-component toner. The one-component toner may be mixed and stirred with carrier particles to form a two-component developer.
[0167] The agitator for performing the external additive treatment is not particularly limited as long as it is an agitator capable of adhering an external additive to the surface of colored resin particles, and examples thereof include agitators similar to those usable in the production of the toner of the first present disclosure. Examples of the external additive include the same additives as those usable in the toner of the first disclosure, and those preferred for the toner of the first disclosure can be similarly preferably used.
[0168] In the toner of the second disclosure, the external additive is usually used in a ratio of 0.05 to 6 parts by mass, preferably 0.2 to 5 parts by mass, based on 100 parts by mass of the colored resin particles. By making the content of the external additive 0.05 parts by mass or more, the occurrence of transfer residue can be suppressed, and by making the content of the external additive 6 parts by mass or less, the occurrence of fogging can be suppressed. The external additive can be used alone or in combination of two or more kinds.
[0169] The toner of the second disclosure has a temperature-tan δ curve that satisfies the formula (II-1) and the formula (II-2), and thus has good storage stability and suppresses a decrease in the blocking temperature (heat resistance temperature). The toner of the second disclosure has a blocking temperature (heat resistance temperature) of preferably 53° C. or higher, more preferably 54° C. or higher, and even more preferably 55° C. or higher.
[0170] The toner of the second disclosure has a temperature-tan δ curve that satisfies the formula (II-1) and the formula (II-2), and thus has good low-temperature fixability and suppresses an increase in fixation temperature. The fixation temperature of the toner of the second disclosure is preferably 170° C. or less, more preferably 160° C. or less, and even more preferably 150° C. or less.
[0171] In addition, in the toner of the second disclosure, the apparent glass transition temperature (Tg2) and the heat generation start temperature are in the specific range, and the temperature-tan δ curve of the toner satisfies the formula (II-1), so that the toner has good storage stability and is easy to suppress the occurrence of blowing out after being left at high temperature. In the toner of the second disclosure, in a blowing out test after being left at high temperature, the time (blow-out time (seconds)) until the phenomenon of the toner spilling out (blow-out) from the developing roller of the cartridge is stopped is preferably 0 to 15 seconds, and a shorter blow-out time is more preferable, and it is even more preferable that no blow-out occurs. In the present disclosure, the blow-out test of the toner after being left at high temperature is performed by filling the toner into a toner cartridge of a developing device of a commercially available non-magnetic one-component developing printer with the toner, and leaving the cartridge filled with the toner in a sealed state so as not to be affected by humidity in a high temperature environment (temperature: 45°C) for 5 days, and then in an environment of 23°C and humidity 50% RH. The toner ejection test can be performed by the same test as the toner ejection test after being left at high temperature in the examples described later. EXAMPLES
[0172] The present disclosure will be described in more detail below with reference to examples and comparative examples, but the present disclosure is not limited to these examples. Note that parts and % are by weight unless otherwise specified. The weight-average molecular weight Mw of the polymer was determined by polystyrene conversion using GPC. The sample for measurement was prepared by dissolving the polymer in tetrahydrofuran (THF) to a concentration of 2 mg / mL, subjecting it to ultrasonic treatment for 10 minutes, and passing it through a 0.45 μm membrane filter to obtain a sample. The measurement conditions were temperature: 40° C., solvent: tetrahydrofuran, flow rate: 1.0 mL / min, concentration: 0.2 wt%, sample injection amount: 100 μL, and the column used was a GPC TSKgel MultiporeHXL-M (30 cm x 2 columns) manufactured by Tosoh Corporation. The measurement was performed under conditions where the linear correlation equation of Log(Mw)-elution time between weight-average molecular weights Mw of 1,000 to 300,000 was 0.98 or more. The weight average molecular weight Mw of the polymer contained in the binder resin in the toner was determined by dissolving the toner in THF as a sample, and using data obtained by subtracting the peaks of the charge control resin, softener, styrene-based thermoplastic elastomer, etc., which were measured in advance, from the GPC results obtained by the above-mentioned measurement method.
[0173] Example I Series: First Toner of the Present Disclosure [Example I-1] 1. Manufacturing of colored resin particles (1) Preparation of polymerizable monomer composition for core: 70 parts of styrene as polymerizable monomers, 30 parts of n-butyl acrylate, 0.1 parts of polymethacrylate macromonomer (manufactured by Toagosei Chemical Industry Co., Ltd., product name: AA6, Tg = 94 ° C), 0.72 parts of divinylbenzene, 1.25 parts of tetraethyl thiuram disulfide as a molecular weight regulator, and 8 parts of CI Pigment Yellow 155 (product name: Toner Yellow 3GP CT, manufactured by Clariant) as a colorant were wet-pulverized using a media-type disperser (manufactured by Asada Iron Works, product name: Picomil). The viscosity of the mixture obtained by wet pulverization was measured by the following method and found to be 974 mPa s. (Method of measuring viscosity) The viscosity was measured using a Brookfield type viscometer (Digital Rheometer DV-I+, manufactured by Brookfield). The mixture obtained by the wet grinding was cooled to 25°C using a thermostatic water bath, and the spindle was rotated at 60 rpm for 1 minute, after which the viscosity was measured. The following spindles were selected according to the viscosity range to be measured. Less than 100 mPa·s: Spindle No.1 100 mPa·s or more but less than 200 mPa·s: Spindle No. 2 200 mPa·s or more and less than 1500 mPa·s: Spindle No. 3
[0174] To the mixture obtained by the wet grinding, 0.5 parts of a charge control resin (styrene acrylic resin containing a quaternary ammonium salt, functional group amount 8% by mass) and 6.0 parts of a synthetic ester wax (pentaerythritol tetrabehenate, melting point 76°C) were added, mixed, and dissolved to prepare a polymerizable monomer composition for a core.
[0175] (2) Preparation of aqueous dispersion medium: Separately, an aqueous solution of 7.3 parts of sodium hydroxide in 50 parts of ion-exchanged water was gradually added to an aqueous solution of 10.4 parts of magnesium chloride in 280 parts of ion-exchanged water with stirring to prepare a magnesium hydroxide colloidal dispersion.
[0176] (3) Preparation of polymerizable monomer for shell: On the other hand, 2 parts of methyl methacrylate and 130 parts of water were subjected to a fine dispersion treatment using an ultrasonic emulsifier to prepare an aqueous dispersion of a polymerizable monomer for the shell.
[0177] (4) Granulation process: The above-mentioned core polymerizable monomer composition was added to the above-mentioned magnesium hydroxide colloidal dispersion liquid (magnesium hydroxide amount: 5.3 parts), further stirred, and 6 parts of t-butylperoxy-2-ethylbutanoate was added thereto as a polymerization initiator. The dispersion liquid to which the polymerization initiator was added was dispersed at a rotation speed of 15,000 rpm using an in-line type emulsifying disperser (manufactured by Pacific Machinery Works, Ltd., product name: Milder) to form droplets of the core polymerizable monomer composition.
[0178] (5) Suspension polymerization process: The dispersion containing droplets of the core polymerizable monomer composition was placed in a reactor and heated to 90°C to carry out a polymerization reaction. After the polymerization conversion rate reached nearly 100%, 0.1 parts of 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide] (manufactured by Wako Pure Chemical Industries, Ltd., trade name: VA-086, water-soluble initiator) was dissolved in the aqueous dispersion of the shell polymerizable monomer and added to the reactor. The temperature was then maintained at 95°C for 4 hours to continue polymerization, and the reaction was stopped by cooling with water to obtain an aqueous dispersion of core-shell type colored resin particles.
[0179] (6) Post-processing: While stirring the aqueous dispersion of colored resin particles, sulfuric acid was added until the pH became 4.5 or less to perform acid washing (25°C, 10 minutes), and the colored resin particles were filtered out, washed with water, and the washing water was filtered. The electrical conductivity of the filtrate was 20 μS / cm. Furthermore, the colored resin particles after the washing and filtration steps were dehydrated and dried to obtain dried colored resin particles.
[0180] (7) Volume average particle size (Dv), number average particle size (Dn) and particle size distribution (Dv / Dn) Approximately 0.1 g of the colored resin particles was weighed out and placed in a beaker, and 0.1 mL of a surfactant aqueous solution (manufactured by Fujifilm, product name: Drywell) was added as a dispersant. 10 to 30 mL of Isoton II was further added to the beaker, and the mixture was dispersed for 3 minutes using a 20 W (Watt) ultrasonic disperser. The volume average particle size (Dv) and number average particle size (Dn) of the colored resin particles were measured using a particle size measuring device (manufactured by Beckman Coulter, product name: Multisizer) under the following conditions: aperture diameter: 100 μm, medium: Isoton II, number of particles measured: 100,000 particles, and the particle size distribution (Dv / Dn) was calculated.
[0181] 2. Toner manufacturing To 100 parts of colored resin particles, 0.2 parts of hydrophobized silica fine particles with an average particle size of 7 nm, 0.76 parts of hydrophobized silica fine particles with an average particle size of 20 nm, and 1.91 parts of hydrophobized silica fine particles with an average particle size of 50 nm were added and mixed using a high-speed mixer (manufactured by Nippon Coke and Engineering Co., Ltd., product name: FM Mixer) to prepare the toner of Example I-1.
[0182] [Examples I-2 to I-11, Comparative Examples I-1 to I-2] The toners of Examples I-2 to I-11 and Comparative Examples I-1 to I-2 were obtained in the same manner as in Example I-1, except that in "(1) Preparation of polymerizable monomer composition for core" in "1. Production of colored resin particles" above, each material was added according to Table 1 below.
[0183] [Table 1]
[0184] The abbreviations in Table 1 are as follows: ST: styrene BA: n-butyl acrylate DVB: Divinylbenzene AA6: Polymethacrylate macromonomer (manufactured by Toa Gosei Chemical Industry Co., Ltd., product name: AA6, Tg = 94°C) TET: Tetraethylthiuram disulfide PY155: CI Pigment Yellow 155 PY93: CI Pigment Yellow 93 The product names of the colorants in Table 1 are as follows: TY3GP-CT: Product name: TonerYellow3GP CT, manufactured by Clariant VY5GD: Product name: VERSAL YELLOW 5GD, manufactured by Synthesia CY3G: Product name: Cromophthal Yellow D 1040, manufactured by BASF In addition, the mass % of ST and DVB in Table 1 refers to the content ratio of the structural unit derived from ST and the content ratio of the structural unit derived from DVB in 100 mass % of the total amount of the binder resin, and is calculated as the content ratio (mass %) of ST or DVB relative to 100 mass % of the total amount of the polymerizable monomers and molecular weight adjusters used in the synthesis of the binder resin. The weight average molecular weight Mw of the polymer contained in the binder resin is within 10% of the value shown in Table 1. 5 This is the value multiplied by
[0185] [Measurement of viscoelasticity] For the toners obtained in each of the examples and comparative examples, a temperature dependency curve of loss tangent (tan δ) was obtained by dynamic viscoelasticity measurement. The dynamic viscoelasticity measurement was performed using a rotating plate rheometer (TA Instruments, ARES-G2) and a crosshatch plate under the following conditions. A test piece was prepared by pouring 0.2 g of the toner into a cylindrical molding machine with a diameter of 8 mm, applying pressure at 1.0 MPa for 30 seconds, and molding into a cylindrical body with a thickness of 3 mm and a diameter of 8 mm. (Conditions for dynamic viscoelasticity measurement) Frequency: 24Hz Sample set: The test piece (3 mm thick) is sandwiched between 8 mm diameter plates with a load of 20 g, the temperature is raised to 80°C to fuse the test piece to the jig, then the temperature is returned to 45°C and the temperature rise is started. Heating rate: 5℃ / min Temperature range: 45℃ to 150℃
[0186] The linearity of the temperature dependency curve of the loss tangent (tan δ) of the toner obtained in each example was such that, from 45°C to the glass transition temperature (Tg) shown in Table 2, tan δ increased rapidly from near 0 to near 1.6 as the temperature increased, and tan δ reached a maximum value at Tg, and from Tg to near 100°C, tan δ decreased to near 0.8 to 0.9 as the temperature increased, and reached a minimum value of tan δ, and from the temperature at the minimum value to 150°C, tan δ increased gradually as the temperature increased, and then became a nearly constant value. As an example, the temperature dependency curve of the loss tangent (tan δ) of the toner obtained in Example I-1 is shown in Figure 1. The dynamic viscoelasticity measurement was performed in the range of 45°C to 150°C, and the measurement results from 45°C to 145°C are shown in Figure 1. In addition, from the obtained temperature-tanδ curve, the loss tangent tanδ(45°C) at 45°C, the glass transition temperature (Tg), the loss tangent tanδ(Tg) at the glass transition temperature (Tg), the loss tangent tanδ(100°C) at 100°C, and the loss tangent tanδ(130°C) at 130°C were obtained for each toner, and the value of (tanδ(Tg)-tanδ(45°C)) / (Tg-45) shown in the above formula (I-1) and the value of (tanδ(130°C)-tanδ(100°C)) / 30 shown in the above formula (I-2) were calculated.
[0187] [Softening temperature (T 1 / 2 ) Measurement The toner obtained in each of the examples and comparative examples was subjected to measurement under the following conditions using a Shimadzu flow tester (product name CFT-500C) at a pressure of 10.0 kgf / cm 2 The softening temperature (T 1 / 2 ) was sought. (Measurement conditions) Starting temperature: 35℃ Heating rate: 3℃ / min Preheat time: 5 minutes Cylinder pressure: 10.0kgf / cm 2 Die hole diameter: 0.5mm Die length: 1.0mm Sample input amount: 1.0~1.3g
[0188] [evaluation] (1) Toner heat resistance 10 g of toner was placed in a 100 mL polyethylene container and sealed, then the container was submerged in a thermostatic water bath set at a predetermined temperature, and after 8 hours, it was taken out. The toner was transferred from the container onto a 42 mesh sieve with as little vibration as possible, and set in a powder measuring instrument (manufactured by Hosokawa Micron Corporation, product name: Powder Tester (registered trademark) PT-R). The sieve amplitude was set to 1.0 mm, and the sieve was vibrated for 30 seconds, after which the mass of the toner remaining on the sieve was measured, and this was taken as the mass of the aggregated toner. The maximum temperature at which the mass of the aggregated toner becomes 0.5 g or less is defined as the heat resistance temperature of the toner. The higher the heat resistance temperature, the less likely the toner is to cause blocking during storage, and the better the storage stability.
[0189] (2) Toner fixing temperature Using a commercially available printer that uses a non-magnetic single-component development method and has been modified so that the temperature of the fixing roll can be changed, the temperature of the fixing roll was changed in increments of 5°C from 120°C, the fixing rate of the toner was measured at each temperature, the relationship between temperature and fixing rate was determined, and the lowest temperature at which a fixing rate of 80% or more was obtained was determined as the fixing temperature of the toner. The lower the fixing temperature, the better the low-temperature fixing ability of the toner. The fixation rate was calculated from the image density ratio before and after the rubbing test in a solid area on a printed test paper. If the image density before the rubbing test is ID(before) and the image density after the rubbing test is ID(after), then fixation rate (%) = [ID(after) / ID(before)] x 100. The rubbing test was performed by attaching the test portion of the test paper to a fastness tester with adhesive tape, placing a load of 500g on it, and rubbing it back and forth five times with a rubbing terminal wrapped in cotton cloth.
[0190] (3) Gloss (luster) A commercially available non-magnetic single-component development printer (24 sheets; print speed = 24 sheets / min) was modified so that the temperature of the fixing roll section could be changed. The toner cartridge in the development device of the printer was filled with 100 g of toner, and then printing paper was set. The toner amount on the solid area of the paper is 0.35 mg / cm 2 After adjusting the printer so that the image was printed as described above, the temperature of the fixing roll (fixing temperature) was set to 170°C, and a 5 cm square solid image was printed on paper (manufactured by Cowans Group, product name: initiative multipurpose paper). The gloss value of the resulting 5 cm square solid area was measured at an incidence angle of 60° using a gloss meter (manufactured by Nippon Denshoku Industries, product name: VGS-SENSOR). The higher the gloss value, the more lustrous the image.
[0191] [Table 2]
[0192] [Consideration] The toner of Comparative Example I-1 has a temperature-tan δ curve in which the value of (tan δ(130° C.)-tan δ(100° C.)) / 30 shown in the above formula (I-2) is −3.0×10 -3 Since the toner of Comparative Example I-1 had a viscoelasticity of 0.1 to 1.0 μm, the fixing temperature was high and the low-temperature fixing property was poor. In addition, since the toner of Comparative Example I-1 was not sufficiently dissolved in THF, the weight average molecular weight Mw of the polymer contained as the binder resin could not be measured. The toner of Comparative Example I-2 has a temperature-tan δ curve in which the value of (tan δ(Tg)-tan δ(45° C.)) / Tg-45 shown in the above formula (I-1) is 7.60×10 -2 Since the toner had the above viscoelasticity, the heat resistance temperature was low, that is, blocking was likely to occur during storage of the toner, and the storage stability was poor. On the other hand, the toners of Examples I-1 to I-11 had viscoelasticity that satisfied the above formula (I-1) and formula (I-2) in the temperature-tan δ curve, and therefore had a high heat resistance, i.e., the toner was less likely to cause blocking during storage, and therefore had excellent storage properties, a low fixing temperature, excellent low-temperature fixing properties, and also excellent gloss.
[0193] Example II Series: Second Toner of the Present Disclosure [Production Example II-1: Production of Magenta Pigment A] 2,5-Di-(4-methylphenylamino)terephthalic acid was cyclized in phosphoric acid to synthesize 2,9-dimethylquinacridone (CI Pigment Red 122). Water was added to the resulting phosphoric acid dispersion of 2,9-dimethylquinacridone, which was then filtered and washed with water. Water was added again to the washed 2,9-dimethylquinacridone to make an aqueous dispersion with a solid content of 20%. Similarly, a water dispersion of quinacridone (CI Pigment Violet 19) with 20% solids was prepared using 2,5-diphenylaminoterephthalic acid. 250 parts of ethanol was added to 250 parts of the aqueous dispersion of dimethylquinacridone (CI Pigment Red 122) with a solid content of 20% and 250 parts of the aqueous dispersion of quinacridone (CI Pigment Violet 19) with a solid content of 20% to obtain a pigment mixture. This mixture was transferred to a container equipped with a cooling tube, and reacted for 5 hours under heating and reflux while grinding the pigment. After the reaction was completed, the pigment was filtered out from the reaction solution, washed, dried, and then pulverized to obtain magenta pigment A, which is a mixed crystal of magenta pigments (i.e., a mixed crystal of CI Pigment Red 122 and CI Pigment Violet 19). The mass ratio of each pigment contained in the mixed crystal was CI Pigment Red 122:CI Pigment Violet 19=1:1.
[0194] [Production Example II-2: Production of Elastomer a] In a pressure-resistant reactor, 23.2 kg of cyclohexane, 1.5 mmol of N,N,N',N'-tetramethylethylenediamine (TMEDA) and 1.70 kg of styrene were added, and while stirring at 40°C, 99.1 mmol of n-butyllithium was added, and polymerization was carried out for 1 hour while raising the temperature to 50°C. The polymerization conversion rate of styrene was 100% by mass. Subsequently, 6.03 kg of isoprene was continuously added to the reactor over 1 hour while controlling the temperature to maintain 50 to 60°C. After the addition of isoprene was completed, polymerization was carried out for another 1 hour to form a styrene-isoprene diblock copolymer. The polymerization conversion rate of isoprene was 100% by mass. Next, 15.0 mmol of dimethyldichlorosilane was added as a coupling agent to carry out a coupling reaction for 2 hours, and a styrene-isoprene-styrene triblock copolymer was formed. After this, 198 mmol of methanol was added as a polymerization terminator, and the reaction was stopped by mixing well, to obtain a reaction liquid containing a block copolymer composition. Then, 0.3 parts of 2,6-di-tert-butyl-p-cresol was added as an antioxidant to 100 parts of the reaction liquid thus obtained (containing 30 parts of polymer component) and mixed, and the mixed solution was dropped little by little into warm water heated to 85 to 95°C to volatilize the solvent and obtain a precipitate, which was then pulverized and dried with hot air at 85°C to recover a block copolymer composition. The content of styrene monomer units in the obtained block copolymer composition (elastomer a) was 24 mass%, and the weight average molecular weight Mw was 106,000.
[0195] [Example II-1] 1. Manufacturing of colored resin particles (1) Preparation of polymerizable monomer composition for core: 74 parts of styrene as polymerizable monomers, 26 parts of n-butyl acrylate, 0.1 part of polymethacrylic acid ester macromonomer (manufactured by Toa Gosei Chemical Industry Co., Ltd., product name: AA6, Tg = 94°C), 0.50 parts of tetraethyl thiuram disulfide as a molecular weight regulator, and 8.0 parts of the magenta pigment A (mixed crystal of CI Pigment Red 122 and CI Pigment Violet 19) obtained in Production Example 1 above as a colorant, were wet-pulverized using a media-type disperser (manufactured by Asada Iron Works Co., Ltd., product name: Picomil). To the mixture obtained by the wet grinding, 10.0 parts of a charge control resin (CCR1: styrene acrylic resin containing a quaternary ammonium salt, functional group amount 1% by mass), 12.0 parts of synthetic ester wax 1 (hexaglycerin octabehenate, melting point 70°C), and 2.0 parts of the elastomer a obtained in Production Example II-2 as a styrene-based thermoplastic elastomer were added, mixed, and dissolved to prepare a polymerizable monomer composition for a core.
[0196] (2) Preparation of aqueous dispersion medium: Separately, an aqueous solution of 7.3 parts of sodium hydroxide in 50 parts of ion-exchanged water was gradually added to an aqueous solution of 10.4 parts of magnesium chloride in 280 parts of ion-exchanged water with stirring to prepare a magnesium hydroxide colloidal dispersion.
[0197] (3) Preparation of polymerizable monomer for shell: On the other hand, 2 parts of methyl methacrylate and 130 parts of water were subjected to a fine dispersion treatment using an ultrasonic emulsifier to prepare an aqueous dispersion of a polymerizable monomer for the shell.
[0198] (4) Granulation process: The above-mentioned core polymerizable monomer composition was added to the above-mentioned magnesium hydroxide colloidal dispersion liquid (magnesium hydroxide amount: 5.3 parts), further stirred, and 6 parts of t-butylperoxy-2-ethylbutanoate was added thereto as a polymerization initiator. The dispersion liquid to which the polymerization initiator was added was dispersed at a rotation speed of 15,000 rpm using an in-line type emulsifying disperser (manufactured by Pacific Machinery Works, Ltd., product name: Milder) to form droplets of the core polymerizable monomer composition.
[0199] (5) Suspension polymerization process: The dispersion containing droplets of the core polymerizable monomer composition was placed in a reactor and heated to 90°C to carry out a polymerization reaction. After the polymerization conversion rate reached nearly 100%, 0.1 parts of 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)-propionamide] (manufactured by Wako Pure Chemical Industries, Ltd., trade name: VA-086, water-soluble initiator) was dissolved in the aqueous dispersion of the shell polymerizable monomer and added to the reactor. The temperature was then maintained at 95°C for 4 hours to continue polymerization, and the reaction was stopped by cooling with water to obtain an aqueous dispersion of core-shell type colored resin particles.
[0200] (6) Post-processing: While stirring the aqueous dispersion of colored resin particles, sulfuric acid was added until the pH became 4.5 or less to perform acid washing (25°C, 10 minutes), and the colored resin particles were filtered out, washed with water, and the washing water was filtered. The electrical conductivity of the filtrate was 20 μS / cm. Furthermore, the colored resin particles after the washing and filtration steps were dehydrated and dried to obtain dried colored resin particles. The volume average particle size (Dv), number average particle size (Dn) and particle size distribution (Dv / Dn) of the obtained colored resin particles were measured in the same manner as in Example I series.
[0201] 2. Toner manufacturing To 100 parts of colored resin particles, 0.2 parts of hydrophobized silica fine particles with an average particle size of 7 nm, 0.76 parts of hydrophobized silica fine particles with an average particle size of 20 nm, and 1.91 parts of hydrophobized silica fine particles with an average particle size of 50 nm were added and mixed using a high-speed mixer (manufactured by Nippon Coke and Engineering Co., Ltd., product name: FM Mixer) to prepare the toner of Example II-1.
[0202] [Examples II-2 to II-17, Comparative Examples II-1 to II-7] The toners of Examples II-2 to II-17 and Comparative Examples II-1 to II-7 were obtained in the same manner as in Example II-1, except that in "(1) Preparation of Core Polymerizable Monomer Composition" of "1. Production of Colored Resin Particles" above, each material was added according to Table 3 below.
[0203] [Table 3]
[0204] The abbreviations in Table 3 are as follows: Among the abbreviations in Table 3, those described in Table 1 are as described above. PB15:3: CI Pigment Blue 15:3 PY214: CI Pigment Yellow 214 SY98: CI Solvent Yellow 98 CCR1: Styrene acrylic resin containing quaternary ammonium salt, functional group amount 1% by mass CCR2: Styrene acrylic resin containing quaternary ammonium salt, functional group amount 0.5 mass% Ester wax 1: Hexaglycerin octabehenate (melting point 70℃) Ester wax 2: Pentaerythritol tetrabehenate (melting point 76°C) Ester wax 3: Pentaerythritol tetrastearate (melting point 76°C) In Table 3, the type of colorant "PY214 / SY98" and the parts "6.4 / 1.28" in Examples II-16 to II-17 and Comparative Examples II-5 to II-6 mean that 6.4 parts of CI Pigment Yellow 214 and 1.28 parts of CI Solvent Yellow 98 were used as colorants. The type of colorant "PY214 / SY98" and the parts "8.0 / 1.6" in Comparative Example II-7 mean that 8.0 parts of CI Pigment Yellow 214 and 1.6 parts of CI Solvent Yellow 98 were used as colorants. The weight average molecular weight Mw of the polymer contained in the binder resin is within 10% of the value shown in Table 3. 4 This is the value multiplied by
[0205] [Measurement of viscoelasticity] For the toners obtained in each of the Examples and Comparative Examples, a temperature dependency curve of loss tangent (tan δ) was obtained by dynamic viscoelasticity measurement similar to that in the Example I series. The linearity of the temperature dependency curve of the loss tangent (tan δ) of the toner obtained in each Example was such that, from 45°C to the glass transition temperature (Tg) shown in Table 4, tan δ increased rapidly from near 0 to near 2.0 as the temperature increased, and tan δ reached a maximum value at Tg, and from Tg to near 100°C, tan δ decreased to near 1.0 to 1.2 as the temperature increased, and reached a minimum value of tan δ, and from the temperature at the minimum value to 150°C, tan δ increased gradually as the temperature increased. As an example, the temperature dependency curve of the loss tangent (tan δ) of the toner obtained in Example II-1 is shown in FIG. 2. The dynamic viscoelasticity measurement was performed in the range of 45°C to 150°C, and FIG. 2 shows the measurement results from 45°C to 145°C. In addition, from the obtained temperature-tanδ curve, the loss tangent tanδ(45°C) at 45°C, the glass transition temperature (Tg), the loss tangent tanδ(Tg) at the glass transition temperature (Tg), the loss tangent tanδ(100°C) at 100°C, and the loss tangent tanδ(130°C) at 130°C were obtained for each toner, and the value of (tanδ(Tg)-tanδ(45°C)) / (Tg-45) shown in the above formula (II-1) and the value of (tanδ(130°C)-tanδ(100°C)) / 30 shown in the above formula (II-2) were calculated.
[0206] [Softening temperature (T 1 / 2 ) Measurement The toner obtained in each of the examples and comparative examples was subjected to measurement under the following conditions using a Shimadzu Corporation flow tester (product name CFT-500C) at a pressure of 5.0 kgf / cm 2 The softening temperature (T 1 / 2 ) was sought. (Measurement conditions) Starting temperature: 35℃ Heating rate: 3℃ / min Preheat time: 5 minutes Cylinder pressure: 5.0kgf / cm 2 Die hole diameter: 0.5mm Die length: 1.0mm Sample input amount: 1.0~1.3g
[0207] [High-speed DSC measurement] For the toner obtained in each Example and Comparative Example, DSC curves were obtained during temperature rise and fall by high-speed differential scanning calorimetry. In the differential scanning calorimetry (DSC) using the high-speed differential scanning calorimeter, silicone oil was applied to the chip sensor using the tip of a brush and spread as a pretreatment of the sample. By applying silicone oil to the chip sensor, the toner after measurement does not fuse to the chip sensor, so that the toner after measurement can be removed and the same chip sensor can be reused. As a result, the baseline becomes stable between samples, and data with good reproducibility can be obtained. About 10 particles of toner were placed on the chip sensor to which silicone oil was applied, and the toner was measured under the following temperature conditions (1) to (5) using an ultra-high-speed DSC device (Mettler Toledo, Flash DSC) under a nitrogen gas flow. (1) Hold at 0°C for 0.1 seconds (2) Heat from 0°C to 150°C at 1000K / sec. (3) Hold at 150°C for 60 seconds. (4) The temperature is decreased from 150°C to 0°C at -1000K / sec. (5) Hold at 0°C for 1 second.
[0208] FIG. 3 shows how to determine the apparent glass transition temperature (Tg2) of a toner when heated at a heating rate of 1000 K / sec in high speed differential scanning calorimetry, and the heat generation initiation temperature of a toner when cooled at a heating rate of 1000 K / sec. The apparent glass transition temperature (Tg2) was determined as the temperature at the intersection of a straight line extending from the low-temperature baseline to the high-temperature side in the DSC curve during heating and a tangent drawn at the step-like change in the glass transition or at the point where the slope of the endothermic peak due to enthalpy relaxation is maximum. The heat generation onset temperature was defined as the temperature at which heat generation begins when the DSC curve during cooling moves away from the previous baseline and an exothermic peak appears.
[0209] [evaluation] The heat resistance temperature of the toner, the fixing temperature of the toner, and the gloss of the image were measured in the same manner as in Example I series. Further, the heat resistance temperature and fixing temperature of the toner of each of the examples and comparative examples were evaluated according to the following evaluation criteria. (Heat resistance temperature evaluation criteria) ◎: 58℃ or higher ○: 53℃ or higher and 57℃ or lower ×: 52℃ or less (Evaluation Criteria for Fixing Temperature) ○: Less than 180℃ ×: 180℃ or higher
[0210] (3) Toner spray test after exposure to high temperatures A commercially available printer using a non-magnetic one-component development system was used, and the toner cartridge of the development device was filled with toner. The cartridge filled with toner was sealed to prevent it from being affected by humidity and left in a high temperature environment (temperature: 45°C) for 5 days, and then in an environment of 23°C and 50% RH, the developing roller mounted on the cartridge was rotated at 400 revolutions per minute (equivalent to a print speed of 40 ppm) using an electric screwdriver (Panasonic EZ6220). This confirmed whether or not the phenomenon of toner spilling (spurting out) from the developing roller of the cartridge occurred. If the phenomenon of toner spilling (spurting out) from the developing roller of the cartridge stopped, the spurting time (seconds) was recorded. If the phenomenon of toner spurting out did not occur, the spurting time was recorded as 0 seconds.
[0211] [Table 4]
[0212] [Consideration] The toners of Comparative Examples II-1, II-2, and II-7 have a temperature-tan δ curve in which the value of (tan δ(130° C.)-tan δ(100° C.)) / 30 shown in the above formula (II-2) is 2.1×10 -3 Since the toner had a viscoelasticity of 0.1 to 100 μm or less, the fixing temperature was high and the low-temperature fixing property was poor. The toners of Comparative Examples II-3 and II-5 have a temperature-tan δ curve in which the value of (tan δ(Tg)-tan δ(45° C.)) / (Tg-45) shown in the above formula (II-1) is 7.60×10 -2 Since the toner had the above viscoelasticity, the heat resistance temperature was low, that is, blocking was likely to occur during storage of the toner, resulting in poor storage stability and poor ejection properties after being left at high temperatures. The toner of Comparative Example II-4 has a temperature-tan δ curve in which the value of (tan δ(Tg)-tan δ(45° C.)) / (Tg-45) shown in the above formula (II-1) is 5.00×10 -2 Since the toner had a viscoelasticity of 0.1 to 100 μm or less, the fixing temperature was high and the low-temperature fixing property was poor. The toner of Comparative Example II-6 has a temperature-tan δ curve in which the value of (tan δ(Tg)-tan δ(45° C.)) / (Tg-45) shown in the above formula (II-1) is 7.60×10 -2 or more, and the value of (tan δ(130° C.)−tan δ(100° C.)) / 30 shown in the formula (II-2) is 4.4×10 -2 Since the composition had the above viscoelasticity, the heat resistance temperature was lower than that of Comparative Example II-5, and the storage stability was further inferior. On the other hand, the toners of Examples II-1 to II-17 had viscoelasticity that satisfied the above formulas (II-1) and (II-2) in the temperature-tan δ curve, and therefore had high heat resistance, i.e., the toners were less likely to cause blocking during storage, and therefore had excellent storage stability, low fixing temperature, excellent low-temperature fixing ability, and excellent gloss. The toners of Examples II-1 to II-17 also had excellent ejection properties after being left at high temperatures.
Claims
1. A toner containing colored resin particles including a binder resin, a colorant, a softener, and a charge control agent, and an external additive, the glass transition temperature (Tg) determined from a temperature dependency curve of the loss tangent (tan δ) of the toner obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz satisfies 45° C.<Tg(° C.)<100° C., The loss tangent (tan δ) at the glass transition temperature (Tg) is 1.291 or more and less than 1.870, and the loss tangent (tan δ) at 130° C. is 1.280 or less, In the temperature dependency curve of the loss tangent (tan δ), when the loss tangent (tan δ) at 45° C. is tan δ(45° C.), the loss tangent (tan δ) at the glass transition temperature (Tg) is tan δ(Tg), the loss tangent (tan δ) at 100° C. is tan δ(100° C.), and the loss tangent (tan δ) at 130° C. is tan δ(130° C.), Formula (I-1): 5.00 × 10 -2 <(tanδ(Tg)-tanδ(45°C)) / (Tg-45)<7.60×10 -2 and Formula (I-2): -3.0×10 -3 <(tanδ(130°C) - tanδ(100°C)) / 30 < 9.8×10 -1 A toner characterized by satisfying the above requirements.
2. Flow tester: Pressure 10.0 kgf / cm 2 The softening temperature (T 1/2 2. The toner according to claim 1, wherein the temperature of the toner is greater than 154°C and less than 220°C.
3. The toner according to claim 1, wherein the lower limit in formula (I-1) is 6.75×10 −2 or more.
4. 4. The toner according to claim 1, wherein in the temperature dependency curve of the loss tangent (tan δ), the loss tangent (tan δ) at 100° C. is 0.800 or more and 1.100 or less, and the loss tangent (tan δ) at 130° C. is 0.800 or more and 1.280 or less.
5. 5. The toner according to claim 1, wherein the binder resin contains a polymer of one or more polymerizable monomers including at least one monovinyl monomer selected from the group consisting of styrene, an acrylic acid ester, and a methacrylic acid ester.
6. The weight average molecular weight of the polymer contained in the binder resin is 3.00×10 5 Above 7.00 x 10 5 6. The toner according to claim 1, wherein:
7. A toner containing colored resin particles including a binder resin, a colorant, a softener, and a charge control agent, and an external additive, the glass transition temperature (Tg) determined from a temperature dependency curve of the loss tangent (tan δ) of the toner obtained by dynamic viscoelasticity measurement at a measurement frequency of 24 Hz satisfies 70° C.<Tg(° C.)<100° C., The loss tangent (tan δ) at the glass transition temperature (Tg) is less than 2.410; In the temperature dependency curve of the loss tangent (tan δ), when the loss tangent (tan δ) at 45° C. is tan δ(45° C.), the loss tangent (tan δ) at the glass transition temperature (Tg) is tan δ(Tg), the loss tangent (tan δ) at 100° C. is tan δ(100° C.), and the loss tangent (tan δ) at 130° C. is tan δ(130° C.), Formula (II-1): 5.00×10 -2 <(tanδ(Tg)-tanδ(45°C)) / (Tg-45)<7.60×10 -2 and Formula (II-2): 2.1×10 -3 <(tanδ(130 °C) - tanδ(100 °C)) / 30 < 4.4×10 -2 A toner characterized by satisfying the above requirements.
8. The toner according to claim 7, wherein the toner has an apparent glass transition temperature (Tg2) of 68° C. to 74° C. when heated at a temperature increasing rate of 1000 K / sec, and a heat generation initiation temperature of 50° C. to 62° C. when cooled at a temperature decreasing rate of 1000 K / sec, as measured by differential scanning calorimetry using a high-speed differential scanning calorimeter.
9. Flow tester: Pressure 5.0 kgf / cm 2 The softening temperature (T 1/2 9. The toner according to claim 7, wherein the temperature of the toner is more than 124°C and less than 159°C.
10. 10. The toner according to claim 7, wherein in the temperature dependency curve of the loss tangent (tan δ), the loss tangent (tan δ) at 100°C is 0.900 or more and 1.400 or less, and the loss tangent (tan δ) at 130°C is 1.000 or more and 2.500 or less.
11. 11. The toner according to claim 7, wherein the binder resin contains a polymer of one or more polymerizable monomers including at least one monovinyl monomer selected from the group consisting of styrene, an acrylic acid ester, and a methacrylic acid ester.
12. The weight average molecular weight of the polymer contained in the binder resin is 2.00×10 4 Above 1.00 x 10 5 12. The toner according to claim 7, wherein:
Citation Information
Patent Citations
Toner for developing electrostatic charge image, device unit and image forming method
JP1997034163A
Toner for electrophotography, developer for electrophotography, and image forming method
JP1999194542A
Image forming method and image forming device
JP1999295918A
Toner for developing electrostatic charge image
JP2000003067A
Toner, image forming method, and process cartridge
JP2006235615A